Toner and two-component developer
The toner composition addresses the technical problem of hot offset and winding resistance by using a crystalline resin and amorphous resin in a domain-matrix structure, achieving enhanced low-temperature fixability and resistance to hot offset and winding.
Patent Information
- Application Number
- CN202011451492.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-13
- Filing Date
- 2020-12-10
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-12-10
AI Technical Summary
Existing toners using crystalline resins for low-temperature fixability suffer from hot offset and winding issues due to poor viscoelasticity in high-temperature regions, and amorphous resins lack rapid melting properties, limiting fixing range and stability in varying environments.
A toner composition comprising a binder resin with a crystalline resin and an amorphous resin, forming a domain-matrix structure with controlled number average domain diameter and monomer unit ratios, enhancing low-temperature fixability and resistance to hot offset and winding.
The proposed solution provides a toner with improved low-temperature fixability, hot offset resistance, and winding resistance by optimizing the domain-matrix structure and composition of the binder resin, ensuring effective fixing properties.
Smart Images

Figure CN112987519B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a toner that can be used in an electrophotographic system, an electrostatic recording system, an electrostatic printing system, and a toner jetting system, and to a two-component developer using the toner. Background Art
[0002] In recent years, with the popularization of full-color electrophotographic copiers, the demand for high-speed printing and energy saving has been increasing. In order to achieve high-speed printing, a technology for melting the toner more quickly in the fixing step has been studied. A technology for shortening various control times during and between jobs in order to increase productivity has also been studied. As a strategy for energy saving, a technology for fixing the toner at a lower temperature in order to reduce energy consumption in the fixing step has been studied.
[0003] It is known that when a crystalline resin having a rapid melting property is used as a main component of a binder resin in a toner, the toner has more excellent low-temperature fixability than a toner having an amorphous resin as a main component. Many toners containing crystalline polyesters as a resin having a rapid melting property have been proposed. However, crystalline polyesters have been problematic in terms of charging stability in a high-temperature and high-humidity environment, and particularly in terms of maintaining charging properties after being left in a high-temperature and high-humidity environment.
[0004] Various toners using a crystalline vinyl resin as another type of crystalline resin having a sharp melting property have also been proposed.
[0005] For example, Japanese Patent Application Laid-Open No. 2014-130243 proposes a toner that achieves both low-temperature fixability and heat-resistant storage stability by using an acrylate-based resin having crystallinity in a side chain.
[0006] The toner of the above patent document can provide both low-temperature fixability and heat-resistant storage stability, and also provide improvement in charging stability which is a weak point of the toner using a crystalline polyester resin to a certain extent. However, it has been found that the toner using a crystalline vinyl resin as a binder resin is prone to hot offset and winding because its viscosity is too low in a high temperature region, and has a narrow temperature range for fixing.
[0007] As a result, studies have been conducted on adding a non-crystalline resin to a crystalline resin in order to increase the viscosity of the toner after melting.
[0008] For example, PTL 2 proposes a toner using a binder resin containing both a crystalline vinyl resin and a polyester resin cross-linked by a carbon-carbon bond. The toner disclosed in WO2019 / 073731 can ensure a fixing range to a certain extent, but further improvement is required. Summary of the invention
[0009] The present disclosure provides a toner that exhibits excellent low-temperature fixability and exhibits both hot offset resistance and wrapping resistance.
[0010] A toner comprising toner particles, the toner particles containing a binder resin comprising a first resin and a second resin, wherein
[0011] The first resin is a crystalline resin,
[0012] The second resin is an amorphous resin,
[0013] The first resin has:
[0014] A first monomer unit represented by the following formula (1);
[0015] a second monomer unit which is at least one selected from the group consisting of a monomer unit represented by the following formula (3) and a monomer unit represented by the following formula (4); and
[0016] The third monomer unit represented by the following formula (5),
[0017] The content ratio of the first monomer unit in the first resin is at least 30.0% by mass.
[0018] The content ratio of the third monomer unit in the first resin is 10.0 mass % to 50.0 mass % and when the SP value (J / cm 3 ) 0.5 By SP 21 When indicating, SP 21 Satisfies the following formula (2):
[0019] 21.00≤SP 21 (2)
[0020] The second resin contains at least one resin selected from the group consisting of a vinyl resin and a hybrid resin in which a vinyl resin and a polyester resin are bonded to each other,
[0021] An observed cross section of the toner has a domain-matrix structure formed of a matrix including a first resin and a domain including a second resin, and
[0022] The number average diameter of the domains is 0.10 to 2.00 μm:
[0023]
[0024] In formula (1), R Z1 represents a hydrogen atom or a methyl group, and R represents an alkyl group having 18 to 36 carbon atoms,
[0025]
[0026] In formula (3), X represents a single bond or an alkylene group having 1 to 6 carbon atoms,
[0027] R 1 Indicates -C≡N,
[0028] -C(=O)NHR 10 (where R 10 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms),
[0029] Hydroxyl,
[0030] -COOR 11 (where R 11 is a hydrogen atom, an alkyl group having 1 to 6 (preferably 1 to 4) carbon atoms, or a hydroxyalkyl group having 1 to 6 (preferably 1 to 4) carbon atoms),
[0031] -NH-C(=O)-N(R 13 )2(where R 13 The groups are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4)),
[0032] -COO(CH2)2NHCOOR 14 (where R 14 is an alkyl group having 1 to 4 carbon atoms) or
[0033] -COO(CH2)2-NH-C(=O)-N(R 15 )2(where R 15 The groups are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms), and
[0034] R 2 represents a hydrogen atom or a methyl group,
[0035] In formula (4), R 3 represents an alkyl group having 1 to 4 carbon atoms, and R 4 represents a hydrogen atom or a methyl group.
[0036]
[0037] In formula (5), R 5 represents a hydrogen atom or a methyl group, and Ph represents a phenyl group.
[0038] According to the present disclosure, a toner that exhibits excellent low-temperature fixing ability and exhibits both hot offset resistance and winding resistance can be provided.
[0039] Further features of the present invention will become apparent from the following description of exemplary embodiments. DETAILED DESCRIPTION
[0040] In the present disclosure, unless otherwise stated, the description of a numerical range such as "from XX to YY" or "XX to YY" includes the numbers of the upper and lower limits of the range.
[0041] In the present disclosure, (meth)acrylate means acrylate and / or methacrylate.
[0042] When a numerical range is described in stages, the upper limit and the lower limit of each of the numerical ranges can be arbitrarily combined.
[0043] The term "monomer unit" describes the reaction form of a monomer material in a polymer. For example, a carbon-carbon bonded portion of the main chain of a vinyl monomer polymerized in a polymer is considered a unit. A vinyl monomer can be represented by the following formula (Z):
[0044]
[0045] In formula (Z), Z1 represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, and more preferably a methyl group), and Z2 represents any substituent. The crystalline resin means a resin that gives a clear endothermic peak in the measurement of differential scanning calorimetry (DSC).
[0046] The toner has toner particles including a binder resin having a first resin and a second resin,
[0047] The first resin is a crystalline resin,
[0048] The second resin is an amorphous resin,
[0049] The first resin has
[0050] The first monomer unit represented by the following formula (1),
[0051] is at least one second monomer unit selected from the group consisting of a monomer unit represented by the following formula (3) and a monomer unit represented by the following formula (4), and
[0052] The third monomer unit represented by the following formula (5),
[0053] The content ratio of the first monomer unit in the first resin is at least 30.0% by mass.
[0054] The content ratio of the third monomer unit in the first resin is 10.0 to 70.0 mass % and when the SP value (J / cm 3 ) 0.5 By SP 21 When indicating, SP 21 Satisfies the following formula (2):
[0055] 21.00≤SP 21 (2)
[0056] The second resin contains at least one resin selected from the group consisting of a vinyl resin and a hybrid resin in which a vinyl resin and a polyester resin are bonded to each other, an observed cross-section of the toner has a domain-matrix structure formed by a matrix including the first resin and domains including the second resin, and a number average diameter of the domains is 0.10 to 2.00 μm.
[0057]
[0058] [In formula (1), R Z1 represents a hydrogen atom or a methyl group, and R represents an alkyl group having 18 to 36 carbon atoms.]
[0059]
[0060] In formula (3), X represents a single bond or an alkylene group having 1 to 6 carbon atoms,
[0061] R 1 Indicates -C≡N,
[0062] -C(=O)NHR 10 (where R 10 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms),
[0063] Hydroxyl,
[0064] -COOR 11 (where R 11 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms (and preferably 1 to 4 carbon atoms) or a hydroxyalkyl group having 1 to 6 carbon atoms (and preferably 1 to 4 carbon atoms), -NH-C(=O)-N(R 13 )2(where R 13 The groups are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (and preferably 1 to 4 carbon atoms),
[0065] -COO(CH2)2NHCOOR 14 (where R 14 represents an alkyl group having 1 to 4 carbon atoms), or
[0066] -COO(CH2)2-NH-C(=O)-N(R 15 )2(where R 15 The groups are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms), and
[0067] R 2 represents a hydrogen atom or a methyl group.
[0068] In formula (4), R 3represents an alkyl group having 1 to 4 carbon atoms, and R 4 represents a hydrogen atom or a methyl group.
[0069]
[0070] [In formula (5), R 5 represents a hydrogen atom or a methyl group, and Ph represents a phenyl group.]
[0071] The inventors of the present invention have found that when a crystalline vinyl resin is used as the main component of the binder resin, the fixing temperature range does not need to be widened even if the viscoelasticity in the high temperature region is impaired by adding an amorphous resin. It should be understood that in some cases, both low-temperature fixing property and hot offset resistance are reduced.
[0072] Furthermore, it was found that there was a correlation between the number average diameter of the domains and the fixing temperature range in the case where the observed cross section of the toner had a domain-matrix structure formed of a matrix including a first resin as a crystalline resin and domains including a second resin as an amorphous resin.
[0073] Regarding this correlation, the inventors of the present invention considered the following matters.
[0074] In the domain-matrix structure of the toner cross section, the matrix exhibits excellent low-temperature fixability by containing the first resin which is a crystalline resin.
[0075] Here, when the number average diameter of the domain exceeds 2.00 μm, when the toner is fixed at low temperature, the crystalline resin contained in the matrix melts, but the amorphous resin contained in the domain is less likely to melt. As a result, the domain is less likely to be fixed on paper, and fixing defects may occur.
[0076] Meanwhile, when the toner is fixed at a high temperature, the viscosity of the matrix including the molten crystalline resin tends to become too low, meaning that hot offset resistance and winding resistance tend to decrease.
[0077] In addition, when the number average diameter of the domain is less than 0.10 μm, or when the crystalline resin and the amorphous resin are compatible with each other and form a uniform structure instead of a domain-matrix structure, the hot offset resistance and the winding resistance tend to decrease. In addition, the rapid melting property of the crystalline resin tends to be lost, and the low temperature fixing property tends to decrease.
[0078] In addition, in the case of a domain-matrix structure in which the matrix is composed of an amorphous resin and the domain is composed of a crystalline resin, the melting characteristics tend to be controlled by the amorphous resin, the rapid melting property of the crystalline resin is not fully exerted, and the low-temperature fixing property tends to decrease.
[0079] In addition, for the observed cross section of the toner, it is preferred to have a domain-matrix structure formed by a matrix composed of a first resin as a crystalline resin and a domain composed of a second resin as an amorphous resin. Even in such a case, the matrix may contain an amorphous resin and the domain may contain a crystalline resin as long as the advantageous effects of the present disclosure are not impaired.
[0080] The number average diameter of the domains is preferably 0.10 to 1.50 μm, and more preferably 0.20 to 1.00 μm.
[0081] The number average diameter of the domains can be controlled by changing the composition of the monomers constituting the crystalline resin, the composition of the monomers constituting the amorphous resin, the toner particle production conditions, and the like.
[0082] In the observed cross section of the toner, the ratio of the area of the domain to the area of the cross section of the toner (hereinafter also simply referred to as the domain area ratio) is preferably 15% to 80%.
[0083] The domain area ratio is preferably 20% to 70%, and more preferably 30% to 60%.
[0084] In the case where the domain area ratio falls within the above range, low-temperature fixability and hot offset resistance of the toner can be achieved at higher levels.
[0085] The domain area ratio can be changed by controlling the mixing ratio of the crystalline resin and the amorphous resin in the binder resin, the difference in polarity between the crystalline resin and the amorphous resin, and the like.
[0086] In general, it is often the case that the resin with a higher blending amount forms the matrix and the resin with a lower blending amount forms the domain. However, since the viscosity of the crystalline resin after melting is low, during the production of the toner particles, in the case where there is a step in which a temperature of at least the melting point of the crystalline resin is applied, the matrix can be formed of the crystalline resin even if the blending mass ratio of the crystalline resin is low. Examples of such production steps include a kneading step in the melt kneading method and a melt adhesion step in the emulsion aggregation method.
[0087] The binder resin contains a first resin, and the first resin is a crystalline resin.
[0088] The first resin has a first monomer unit represented by the following formula (1).
[0089] In addition, the content ratio of the first monomer unit in the first resin is at least 30.0% by mass.
[0090]
[0091] In formula (1), R Z1represents a hydrogen atom or a methyl group, and R represents an alkyl group having a carbon number of 18 to 36. R is preferably an alkyl group having a carbon number of 18 to 30. In addition, the alkyl group preferably has a linear structure.
[0092] The first monomer unit has an alkyl group having 18 to 36 carbon atoms represented by R on a side chain, and by having this moiety, the first resin tends to show crystallinity.
[0093] By setting the content ratio of the first monomer unit in the first resin to at least 30.0% by mass, the first resin exhibits crystallinity and low-temperature fixing property is improved.
[0094] When the content ratio of the first monomer unit in the first resin is less than 30.0% by mass, the first resin is less likely to show crystallinity and the low-temperature fixability is deteriorated. The content ratio is preferably at least 40.0% by mass, and more preferably at least 50.0% by mass. However, the upper limit of the content ratio is preferably less than 90.0% by mass, not more than 80.0% by mass, or not more than 70.0% by mass.
[0095] In addition, the first resin exhibits excellent charge retention in a high-temperature and high-humidity environment compared to crystalline polyester, which is a conventionally known crystalline resin, probably because the first resin has a structure exhibiting crystallinity in a side chain.
[0096] If the SP value (J / cm 3 ) 0.5 By SP 11 Indicates that SP 11 It is preferably less than 20.00, more preferably not more than 19.00, and further preferably not more than 18.40. The lower limit of the SP value is not particularly limited, but is preferably at least 17.00.
[0097] The first monomer unit represented by formula (1) is preferably derived from a monomer selected from 18-36 A monomer unit of at least one (first polymerizable monomer) selected from the group consisting of alkyl (meth)acrylates.
[0098] Each has C 18-36 Examples of the alkyl (meth)acrylates include 18-36 (Meth)acrylates of linear alkyl groups [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, behenyl (meth)acrylate, lauryl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, triacontyl (meth)acrylate, tridodecyl (meth)acrylate, etc.] and each having C 18-36Branched alkyl (meth)acrylates [2-decyltetradecyl (meth)acrylate, etc.].
[0099] Among them, at least one selected from the group consisting of (meth)acrylates having a linear alkyl group having a carbon number of 18 to 36 is preferred from the viewpoint of low temperature fixability of the toner. At least one selected from the group consisting of (meth)acrylates having a linear alkyl group having a carbon number of 18 to 30 is more preferred. At least one selected from the group consisting of linear stearyl (meth)acrylate and behenyl (meth)acrylate is still more preferred.
[0100] The first monomer unit may be one monomer or a combination of at least two monomers.
[0101] The first resin has a second monomer unit which is different from the first monomer unit and is at least one selected from the group consisting of a monomer unit represented by the following formula (3) and a monomer unit represented by the following formula (4).
[0102] In addition, if the SP value (J / cm 3 ) 0.5 By SP 21 Indicates that SP 21 Satisfies the following formula (2). In addition, SP 21 More preferably, the following formula (2)' is satisfied.
[0103] 21.00≤SP 21 (2)
[0104] 21.00≤SP 21 ≤40.00 (2)'
[0105]
[0106] In formula (3), X represents a single bond or an alkylene group having 1 to 6 carbon atoms,
[0107] R 1 Indicates -C≡N,
[0108] -C(=O)NHR 10 (where R 10 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms),
[0109] Hydroxyl,
[0110] -COOR 11 (where R 11 is an alkyl group having 1 to 6 carbon atoms (and preferably 1 to 4 carbon atoms) or a hydroxyalkyl group having 1 to 6 carbon atoms (and preferably 1 to 4 carbon atoms),
[0111] -NH-C(=O)-N(R 13 )2(where R 13 The groups are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (and preferably 1 to 4 carbon atoms),
[0112] -COO(CH2)2NHCOOR 14 (where R 14 is an alkyl group having 1 to 4 carbon atoms), or
[0113] -COO(CH2)2-NH-C(=O)-N(R 15 )2(where R 15 The groups are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms), and
[0114] R 2 represents a hydrogen atom or a methyl group.
[0115] In formula (4), R 3 represents an alkyl group having 1 to 4 carbon atoms and R 4 represents a hydrogen atom or a methyl group.
[0116] The first resin contains the second monomer unit, and because the crystalline resin shows high polarity, adhesion to fixing paper is improved and cohesive force between molten toner particles is improved. As a result, scratch resistance is improved.
[0117] Examples of the second polymerizable monomer forming the second monomer unit include the kinds given below. In addition, the second polymerizable monomer may be one kind of monomer or a combination of at least two kinds.
[0118] Monomers containing nitrile groups; for example, acrylonitrile and methacrylonitrile.
[0119] Hydroxyl-containing monomers; for example, 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate.
[0120] Amino group-containing monomers; for example, acrylamide, and monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms and having an ethylenically unsaturated bond (acrylic acid, methacrylic acid, etc.) using a known method.
[0121] Urea group-containing monomer: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amines (n-butylamine, tert-butylamine, propylamine, isopropylamine, etc.), secondary amines (di-n-ethylamine, di-n-propylamine, di-n-butylamine, etc.), aniline, cyclohexylamine, etc.] with an isocyanate having 2 to 30 carbon atoms and having an ethylenically unsaturated bond using a known method.
[0122] Carboxyl group-containing monomers: for example, methacrylic acid, acrylic acid and 2-carboxyethyl (meth)acrylate.
[0123] Wherein, it is preferred to use a monomer with nitrile group, amino, carbamate group, hydroxyl or urea group. More preferably, the monomer is a monomer with ethylenically unsaturated bonds and selected from at least one functional group in the group consisting of nitrile group, amino, carbamate group, hydroxyl and urea group. By using these monomers, the charge rise performance in the low humidity environment is further improved. Wherein, from the viewpoint of showing high electron attractivity and increasing charge transfer speed, nitrile group is more preferred.
[0124] At least one vinyl ester selected from the group consisting of vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprylate, vinyl laurate, vinyl myristic acid, vinyl palmitate, vinyl stearate, vinyl pivalate and vinyl octanoate can be used as the second polymerizable monomer.
[0125] Vinyl esters are a non-conjugated monomer and easily maintain moderate reactivity with the first polymerizable monomer, and thus tend to improve the crystallinity of the first resin and tend to show better low-temperature fixability and heat-resistant storage stability.
[0126] The second polymerizable monomer preferably has an ethylenically unsaturated bond, and more preferably has one ethylenically unsaturated bond.
[0127] The content ratio of the second monomer unit in the first resin is preferably at least 0.1 mass%, at least 1.0 mass%, or at least 5.0 mass%, and preferably not more than 70.0 mass%, not more than 30.0 mass%, or not more than 20.0 mass%. When the content ratio is 5.0 mass% to 70.0 mass%, an improvement effect of scratch resistance tends to be achieved.
[0128] In addition, the SP expressed in the above formula (2) can be 21 A monomer unit of is selected as the second monomer unit.
[0129] In addition, the first resin has a third monomer unit represented by formula (5) derived from styrene or α-methylstyrene.
[0130]
[0131] [In formula (5), R 5 represents a hydrogen atom or a methyl group, and Ph represents a phenyl group.]
[0132] From the viewpoint of charge retention, the content ratio of the third monomer unit in the first resin is 10.0% to 50.0% by mass. The content ratio of the third monomer unit in the first resin is preferably at least 15.0% by mass or at least 20.0% by mass, and preferably not more than 40.0% by mass.
[0133] In addition, the first resin may contain other monomer units in an amount that does not impair the mass ratio of the first monomer unit, the second monomer unit, and the third monomer unit.
[0134] The first resin is preferably a vinyl polymer. The vinyl polymer may be, for example, a polymer of a monomer containing an ethylenically unsaturated bond. The ethylenically unsaturated bond is a free radical polymerizable carbon-carbon double bond, and examples include vinyl, propylene, acryloyl, methacryloyl, and the like.
[0135] From the viewpoint of improving the charging property in a high temperature and high humidity environment, the acid value Ava of the first resin as a crystalline resin is preferably not more than 50.0 mgKOH / g, and more preferably not more than 30.0 mgKOH / g. There is no particular restriction on its lower limit, but it is preferably at least 0 mgKOH / g, and, from the viewpoint of improving the charge rising performance, it is preferably at least 0.5 mgKOH / g, and more preferably at least 1.0 mgKOH / g.
[0136] From the viewpoint of improving the charging performance in a high temperature and high humidity environment, the hydroxyl value OHVa of the first resin as a crystalline resin is preferably not more than 50.0 mgKOH / g, and more preferably not more than 30.0 mgKOH / g. There is no particular restriction on the lower limit thereof, but it is preferably at least 0 mgKOH / g, and, from the viewpoint of improving the charge rise performance, it is preferably at least 0.5 mgKOH / g, and more preferably at least 1.0 mgKOH / g.
[0137] The weight average molecular weight (Mw) of tetrahydrofuran (THF) soluble matter in the first resin as a crystalline resin measured by gel permeation chromatography (GPC) is preferably 10,000 to 200,000, and more preferably at least 20,000 and not more than 150,000. If the weight average molecular weight (Mw) of the THF soluble matter falls within the above range, elasticity at a temperature near room temperature is easily maintained.
[0138] In addition, the melting point of the first resin as a crystalline resin is preferably 50 to 80° C., and more preferably 53 to 70° C. If the melting point is at least 50° C., heat resistant storage stability is improved, and if the melting point is not more than 80° C., low temperature fixability is improved.
[0139] From the viewpoint of promoting the formation of a domain-matrix structure, the content of the first resin which is a crystalline resin in the binder resin is preferably at least 30% by mass, at least 40% by mass or at least 50% by mass, and is preferably not more than 95% by mass, not more than 90% by mass, not more than 80% by mass or not more than 70% by mass.
[0140] The binder resin contains a second resin, and the second resin is a non-crystalline resin.
[0141] The second resin as the non-crystalline resin contains at least one resin selected from the group consisting of vinyl resins and hybrid resins in which a vinyl resin and a polyester resin are bonded to each other.
[0142] Generally, the SP value of the vinyl resin is lower than that of the polyester resin and is close to the SP value of the first resin which is a crystalline resin. The close SP value indicates that the resins have similar polarities and the resins tend to be compatible with each other. Therefore, it is easier to control the number average diameter of the domains in the domain-matrix structure within the above range than with a polyester resin.
[0143] If the SP value of the first resin is SP1 (J / cm 3 ) 0.5 The SP value of the second resin is expressed by SP2 (J / cm 3 ) 0.5 , it is preferred that the relationship represented by the following formula is satisfied from the viewpoint of facilitating the formation of a domain-matrix structure and facilitating the control of the number average diameter of the domains in the domain-matrix structure within the above range.
[0144] 19.0≤SP1
[0145] 0.3≤SP2-SP1≤1.3
[0146] More preferably, the values of SP1 and SP2 satisfy the following relationship.
[0147] 19.0≤SP1≤21.0
[0148] 0.4≤SP2-SP1≤1.0
[0149] In the case of using a hybrid resin in which a vinyl resin and a polyester resin are combined with each other, the content ratio of the vinyl resin in the hybrid resin is preferably at least 10 mass %, at least 20 mass %, at least 40 mass %, at least 60 mass % or at least 80 mass %, and is preferably not more than 100 mass % or not more than 90 mass %.
[0150] The content of the second resin as a non-crystalline resin in the binder resin is preferably at least 4 mass %, at least 5 mass %, at least 10 mass %, at least 20 mass % or at least 30 mass %, and is preferably not more than 70 mass %, not more than 60 mass % or not more than 50 mass %.
[0151] Examples of the vinyl resin include polymers of polymerizable monomers containing an ethylenically unsaturated bond. The ethylenically unsaturated bond is a carbon-carbon double bond capable of radical polymerization, and examples thereof include a vinyl group, an acryl group, an acryloyl group, and a methacryloyl group.
[0152] Examples of the polymerizable monomer include those listed below.
[0153] Styrene monomers, such as o-methylstyrene, m-methylstyrene, p-methylstyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-n-butylstyrene, p-tert-butylstyrene, p-n-hexylstyrene, p-n-octylstyrene, p-n-nonylstyrene, p-n-decylstyrene, p-n-laurylstyrene, p-methoxystyrene, p-chlorostyrene, 3,4-dichlorostyrene, m-nitrostyrene, o-nitrostyrene and p-nitrostyrene;
[0154] Acrylic acid and acrylic acid esters, such as methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, n-octyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, 2-chloroethyl acrylate and phenyl acrylate;
[0155] α-Methylene aliphatic monocarboxylic acids and their esters, for example methacrylic acid, methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, phenyl methacrylate, dimethylaminoethyl methacrylate and diethylaminoethyl methacrylate;
[0156] As well as acrylonitrile, methacrylonitrile, acrylamide, etc.
[0157] Also, acrylic acid and methacrylic acid esters, such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate and 2-hydroxypropyl (meth)acrylate; and hydroxyl-containing polymerizable monomers, such as 4-(1-hydroxy-1-methylbutyl)styrene and 4-(1-hydroxy-1-methylhexyl)styrene. One of these polymerizable monomers may be used alone, or a combination of a plurality thereof may be used.
[0158] In addition to the above-mentioned monomers, various polymerizable monomers capable of vinyl polymerization may be used in the vinyl resin as needed.
[0159] Examples of such polymerizable monomers include those listed below.
[0160] Unsaturated monoolefins, such as ethylene, propylene, butylene and isobutylene; unsaturated polyolefins, such as butadiene and isoprene; halogenated vinyl compounds, such as vinyl chloride and vinylidene chloride, vinyl bromide and vinyl fluoride; vinyl esters, such as vinyl acetate, vinyl propionate and vinyl benzoate; vinyl ethers, such as vinyl methyl ether, vinyl ethyl ether and vinyl isobutyl ether; vinyl ketones, such as vinyl methyl ketone, vinyl hexyl ketone and methyl isopropenyl ketone; N-vinyl compounds, such as N-vinyl pyrrole, N-vinyl carbazole, N-vinyl indole and N-vinyl pyrrolidone; vinyl naphthalene compounds; unsaturated dibasic acids, such as maleic acid, citraconic acid, itaconic acid, alkenyl succinic acid compounds, fumaric acid and mesaconic acid; unsaturated and dibasic acid anhydrides, such as maleic anhydride, citraconic anhydride, itaconic anhydride and alkenyl succinic anhydride compounds; half esters of unsaturated basic acids, such as methyl maleate half ester, ethyl maleate half ester, butyl maleate half ester, methyl citraconic acid half ester, ethyl citraconic acid half ester, butyl citraconic acid half ester, methyl itaconate half ester, alkenyl succinic acid half ester, methyl fumarate half ester and ethyl mesaconic acid half ester; unsaturated basic acid esters, such as dimethyl maleate and dimethyl fumarate; anhydrides of α,β-unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid and cinnamic acid; anhydrides of these α,β-unsaturated acids and lower fatty acids; and carboxyl-containing polymerizable monomers, such as alkenyl malonic acid compounds, alkenyl glutaric acid compounds, alkenyl adipic acid compounds, and anhydrides and monoesters of these.
[0161] Furthermore, the vinyl resin may be a polymer cross-linked using a cross-linkable polymerizable monomer such as those exemplified below, as required.
[0162] Examples of the cross-linkable polymerizable monomer include those listed below.
[0163] Aromatic divinyl compounds; diacrylate compounds connected via an alkyl chain; diacrylate compounds connected via an alkyl chain containing an ether bond; diacrylate compounds connected via a chain including an aromatic group and an ether bond; polyester type diacrylate compounds; and multifunctional crosslinking agents.
[0164] Examples of such aromatic divinyl compounds include divinylbenzene and divinylnaphthalene.
[0165] Examples of such diacrylate compounds linked via an alkyl chain include ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, and compounds in which the acrylate moiety in the above compounds is substituted with a methacrylate moiety.
[0166] The vinyl resin is preferably a polymer including at least one polymerizable monomer selected from the group consisting of styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-butylstyrene, p-tert-butylstyrene, p-hexylstyrene, p-octylstyrene, p-nonylstyrene, p-decylstyrene, p-laurylstyrene, p-methoxystyrene, p-chlorostyrene, 3,4-dichlorostyrene, m-nitrostyrene, o-nitrostyrene, p-nitrostyrene, acrylic acid, methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, n-octyl acrylate, lauryl acrylate Esters, 2-ethylhexyl acrylate, stearyl acrylate, 2-chloroethyl acrylate, phenyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, phenyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, acrylonitrile, methacrylonitrile, acrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 4-(1-hydroxy-1-methylbutyl)styrene and 4-(1-hydroxy-1-methylhexyl)styrene.
[0167] In addition, the vinyl resin may be a copolymer of at least one polymerizable monomer selected from the group listed above and at least one cross-linking polymerizable monomer selected from the group consisting of divinylbenzene, divinylnaphthalene, ethylene glycol diacrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, ethylene glycol dimethacrylate, 1,3-butanediol dimethacrylate, 1,4-butanediol dimethacrylate, 1,5-pentanediol dimethacrylate, 1,6-hexanediol dimethacrylate, and neopentyl glycol dimethacrylate. The content of the cross-linking monomer in the polymer may be about 0.5% to 5.0% by mass.
[0168] Styrene monomers, acrylate monomers, and methacrylate monomers can be given as preferred examples of the polymerizable monomers listed above. A combination of styrene and n-butyl acrylate is preferred. In addition, the number average diameter of the domain containing the second resin as the amorphous resin can be controlled by adjusting the number of carbon atoms in the alkyl group bonded to the ester portion of the acrylate monomer or the methacrylate monomer.
[0169] In the case where the number of carbon atoms is large (for example, in the case where the number of carbon atoms in the alkyl group bonded to the ester portion is at least 8, such as in the case of n-octyl acrylate or lauryl acrylate), the interaction with the first monomer unit present in the crystalline resin becomes stronger, and the compatibility with the monomer unit increases. As a result, the number average diameter of the domain tends to decrease, and in the opposite case where the number of carbon atoms is small, the number average diameter of the domain tends to increase.
[0170] The second resin as the amorphous resin preferably has a monomer unit represented by the following formula (5). In the case where the second resin has a monomer unit represented by the following formula (5), the content ratio of the monomer unit represented by the following formula (5) in the second resin is preferably at least 30.0% by mass, at least 50.0% by mass, or at least 70.0% by mass, and is preferably not more than 95.0% by mass or not more than 90.0% by mass.
[0171]
[0172] In formula (5), R 5 represents a hydrogen atom or a methyl group, and Ph represents a phenyl group. The phenyl group may have a substituent.
[0173] By having a phenyl group, the monomer unit represented by the formula (5) improves charge retention properties particularly in a high-temperature and high-humidity environment.
[0174] In addition, in the case where both the second resin and the first resin contain a monomer unit represented by the above formula (5), an interaction derived from π-electrons tends to occur between the phenyl groups contained in the first resin and the second resin. As a result, it is easier to control the number average diameter of the domain within the above numerical range. In addition, the charge retention in a high temperature and high humidity environment is further improved.
[0175] A polymerization initiator may be used to produce the vinyl resin. From the viewpoint of efficiency, the polymerization initiator may be used in an amount of 0.05 to 10 parts by mass relative to 100 parts by mass of the polymerizable monomer.
[0176] Examples of the polymerization initiator include those listed below.
[0177] 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobisisobutyric acid dimethyl ester, 1,1'-azobis(1-cyclohexanecarbonitrile), 2-carbamoylazoisobutyronitrile, 2,2'-azobis(2,4,4-trimethylpentane), 2-phenylazo-2, 4-Dimethyl-4-methoxyvaleronitrile, 2,2'-azobis(2-methylpropane), ketone peroxides [e.g., methyl ethyl ketone peroxide, acetylacetone peroxide, and cyclohexanone peroxide], 2,2-bis(tert-butylperoxy)butane, tert-butyl hydroperoxide, isopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, α,α'-bis(tert-butyl) Peroxyisopropyl)benzene, isobutyl peroxide, octanoyl peroxide, decanoyl peroxide, lauroyl peroxide, 3,5,5-trimethylhexanoyl peroxide, benzoyl peroxide, m-toluoyl peroxide, diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di-2-ethoxyethyl peroxydicarbonate, dimethoxyisopropyl peroxydicarbonate, di(3-methyl-3-methoxybutyl) peroxycarbonate , acetyl peroxysulfonylcyclohexane, t-butyl peroxyacetate, t-butyl peroxyisobutyrate, t-butyl peroxyneodecanoate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxylaurate, t-butyl peroxybenzoate, t-butyl peroxyisopropyl carbonate, di-t-butyl peroxyisophthalate, t-butyl peroxyallyl carbonate, t-amyl peroxy-2-ethylhexanoate, di-t-butyl peroxyhexahydroterephthalate and di-t-butyl peroxyazelaate.
[0178] The polyester resin used in conventional toners can be advantageously used as the polyester resin for forming a hybrid resin in which a vinyl resin and a polyester resin are bonded to each other. Examples of monomers that can be used in the polyester resin include polyols (diols or trivalent or higher polyols), polycarboxylic acids (dicarboxylic acids or trivalent or higher polycarboxylic acids), and anhydrides and lower alkyl esters thereof.
[0179] Examples of the polyols include those listed below.
[0180] Examples of the diols include the bisphenol derivatives listed below.
[0181] Polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene (3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene (2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene (2.0)-polyoxyethylene (2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene (6)-2,2-bis(4-hydroxyphenyl)propane, etc.
[0182] Examples of other polyols include those listed below.
[0183] Ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polybutylene glycol, sorbitol, 1,2,3,6-hexanetetraol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,4,5-pentanetriol, glycerol, 2-methylpropylenetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, 1,3,5-trihydroxymethylbenzene.
[0184] One of these polyols may be used alone or a plurality of them may be used.
[0185] Examples of the polycarboxylic acid include those listed below.
[0186] Examples of dicarboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-laurylsuccinic acid, isolaurylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctenylsuccinic acid, isooctylsuccinic acid, and anhydrides and lower alkyl esters of these acids. Among them, maleic acid, fumaric acid, terephthalic acid and n-dodecenylsuccinic acid are preferred.
[0187] Examples of trivalent or higher polycarboxylic acids and their anhydrides and lower alkyl esters include those listed below.
[0188] 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxy-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxy)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, and anhydrides and lower alkyl esters of these acids.
[0189] Among them, 1,2,4-benzenetricarboxylic acid (trimellitic acid) and its derivatives are preferred due to their low cost and easy reaction control.
[0190] One of these polycarboxylic acids may be used alone or a plurality of them may be used.
[0191] There is no particular limitation on the production method of the polyester resin, and a known method can be used. For example, the polyester resin can be produced by simultaneously adding the above-mentioned polyol and polycarboxylic acid and then polymerizing by means of esterification reaction, transesterification reaction or condensation reaction. In addition, the polymerization temperature is not particularly limited, but preferably falls within the range of 180° C. to 290° C. When polymerizing the polyester resin, a polymerization catalyst such as a titanium-based catalyst, a tin-based catalyst, zinc acetate, antimony trioxide or germanium dioxide can be used.
[0192] The polyester resin used for the amorphous resin is preferably obtained by polycondensation using a titanium-based catalyst and / or a tin-based catalyst.
[0193] An example of a method for producing a hybrid resin in which a vinyl resin and a polyester resin are combined with each other is a method involving polymerization using a compound capable of reacting with monomers that produce both resins (hereinafter referred to as a "bi-reactive compound").
[0194] Examples of the bireactive compound include compounds such as fumaric acid, acrylic acid, methacrylic acid, citraconic acid, maleic acid, and dimethyl fumarate among monomers of polycondensation resins and monomers of addition resins. Among them, fumaric acid, acrylic acid, and methacrylic acid can be advantageously used.
[0195] From the viewpoint of improving the charging performance in a high temperature and high humidity environment, the acid value AVi of the second resin as an amorphous resin is preferably not more than 50.0 mgKOH / g, and more preferably not more than 30.0 mgKOH / g. There is no particular restriction on its lower limit, but it is preferably at least 0 mgKOH / g, and, from the viewpoint of improving the charge rise performance, it is preferably at least 0.5 mgKOH / g, and more preferably at least 1.0 mgKOH / g.
[0196] From the viewpoint of improving the charging performance in a high temperature and high pressure environment, the hydroxyl value OHVi of the second resin as an amorphous resin is preferably not more than 50.0 mgKOH / g, and more preferably not more than 30.0 mgKOH / g. There is no particular restriction on its lower limit, but it is preferably at least 0 mgKOH / g, and, from the viewpoint of improving the charge rise performance, it is preferably at least 0.5 mgKOH / g, and more preferably at least 1.0 mgKOH / g.
[0197] From the viewpoint of improving the scratch resistance of the fixed image, if the acid value of the first resin is represented by AVa and the acid value of the second resin is represented by AVi, it is preferred that the values of Ava and AVi satisfy the following formulas (6) and (7). In addition, it is more preferred that the values of Ava and AVi satisfy the following formulas (6)' and (7)'.
[0198] 0.5mgKOH / g≤AVa≤30.0mgKOH / g (6)
[0199] 1.0mgKOH / g≤AVa≤25.0mgKOH / g (6)'
[0200] 0.5mgKOH / g≤AVi≤30.0mgKOH / g (7)
[0201] 1.0mgKOH / g≤AVi≤25.0mgKOH / g (7)'
[0202] The case where the above formula is satisfied means a case where, for example, a certain amount of carboxyl groups are present in both the first resin which is a crystalline resin and the second resin which is an amorphous resin.
[0203] In this case, it is thought that hydrogen bonding is promoted by carboxyl groups at the interface between the matrix of the crystalline resin and the domains of the amorphous resin. Therefore, it is thought that when a fixed image is scratched, scratch resistance is improved because the toner is less likely to break at the interface between the matrix and the domain.
[0204] If the acid value of the first resin is represented by AVa and the acid value of the second resin is represented by AVi, it is preferred that the values of Ava and AVi satisfy the following formula (8). In addition, it is more preferred that the values of Ava and AVi satisfy the following formula (8)'.
[0205] 0mgKOH / g≤|AVa-AVi|≤20.0mgKOH / g (8)
[0206] 0mgKOH / g≤|AVa-AVi|≤15.0mgKOH / g (8)'
[0207] From the viewpoint of improving the scratch resistance of the fixed image, if the hydroxyl value of the first resin is represented by OHVa and the hydroxyl value of the second resin is represented by OHVi, it is preferred that the values of OHVa and OHVi satisfy the following formulas (9) and (10). In addition, it is more preferred that the values of OHVa and OHVi satisfy the following formulas (9)' and (10)'.
[0208] 0.5mgKOH / g≤OHVa≤30.0mgKOH / g (9)
[0209] 1.0mgKOH / g≤OHVa≤24.0mgKOH / g (9)'
[0210] 0.5mgKOH / g≤OHVi≤30.0mgKOH / g (10)
[0211] 1.0mgKOH / g≤OHVi≤24.0mgKOH / g (10)'
[0212] If the hydroxyl value of the first resin is represented by OHVa and the hydroxyl value of the second resin is represented by OHVi, it is preferred that the values of OHVa and OHVi satisfy the following formulas (11) and (11)'.
[0213] 0mgKOH / g≤|OHVa-OHVi|≤20.0mgKOH / g (11)
[0214] 0mgKOH / g≤|OHVa-OHVi|≤15.0mgKOH / g (11)'
[0215] The first resin and the second resin may have an acid value or a hydroxyl value, or both an acid value and a hydroxyl value.
[0216] The weight average molecular weight (Mw) of tetrahydrofuran (THF) soluble matter in the second resin as the amorphous resin measured by gel permeation chromatography (GPC) is preferably 20,000 to 1,000,000, and more preferably 50,000 to 150,000. If the weight average molecular weight (Mw) of the THF soluble matter falls within the above range, elasticity at a temperature close to room temperature is easily maintained.
[0217] In addition, from the viewpoint of hot offset resistance, the softening point of the second resin as the amorphous resin is preferably at least 100° C., at least 110° C., at least 115° C., or at least 120° C., and is preferably not more than 180° C. or not more than 160° C. For example, in the case where the softening point of the second resin is 120° C. to 160° C., low-temperature fixability and hot offset resistance can be achieved at a high level.
[0218] From the viewpoint of hot offset resistance, the content ratio of tetrahydrofuran (THF)-insoluble matter in the second resin is preferably at least 3% by mass.
[0219] The binder resin may further contain a third resin. The third resin preferably contains a resin formed by combining the first resin and the second resin, and more preferably a resin formed by combining the first resin and the second resin. In the case where the binder resin contains the third resin, the winding resistance is further improved. For example, the third resin preferably has a structure formed by at least partially combining the first resin and the second resin.
[0220] Methods of connecting the first resin to the second resin include a method of cross-linking by applying a radical reaction initiator to a mixture obtained by melting or fusing the first resin and the second resin, a method of cross-linking using a cross-linking agent having a functional group reactive with both the first resin and the second resin, and the like.
[0221] The radical polymerization initiator used in the cross-linking method using the radical reaction initiator is not particularly limited, and may be an inorganic peroxide, an organic peroxide, an azo compound, etc. These radical reaction initiators may also be combined.
[0222] When both the first resin and the second resin have carbon-carbon unsaturated bonds, these bonds are broken when the first resin and the second resin are cross-linked. When one or both of the first resin and the second resin do not have carbon-carbon unsaturated bonds, the two are cross-linked by extracting hydrogen atoms bonded to carbon atoms contained in the first resin and / or the second resin. In this case, the free radical reaction initiator is more preferably an organic peroxide having a strong hydrogen abstraction ability.
[0223] There is no particular limitation on the cross-linking agent having a functional group reactive with both the first resin and the second resin, and known cross-linking agents may be used, such as a cross-linking agent having an epoxy group, a cross-linking agent having an isocyanate group, a cross-linking agent having an oxazoline group, a cross-linking agent having a carbodiimide group, a cross-linking agent having a hydrazide group, a cross-linking agent having an aziridine group, and the like.
[0224] In the method of cross-linking using a cross-linking agent having a functional group reactive with both the first resin and the second resin, both the first and second resins must have a functional group reactive with the cross-linking agent.
[0225] Toner may be manufactured using a resin in which at least parts of the first resin and the second resin crosslinked by the above method are linked together (ie, a resin composition containing the first resin and the second resin and a third resin obtained by crosslinking the first resin and the second resin).
[0226] When the toner is produced by a melt kneading method, toner particles containing a resin including a first resin linked to a second resin can be produced by melt kneading a raw material mixture containing the first resin and the second resin in the presence of the above radical reaction initiator or crosslinking agent.
[0227] For example, the third resin is preferably a resin obtained by adding a radical reaction initiator while melt-kneading the second resin and the first resin to thereby cause a crosslinking reaction.
[0228] When the third resin is manufactured using the first resin and the second resin, at least part of the first resin and the second resin are connected together to form the third resin. This obtains a binder resin containing the first resin, the second resin and the third resin.
[0229] The binder resin containing the first resin, the second resin and the third resin can also be obtained by connecting at least part of the first resin and the second resin. The binder resin can also be obtained by separately manufacturing the third resin and then mixing it with the first resin and the second resin.
[0230] The content of the third resin in the binder resin is preferably 1.0% by mass to 20.0% by mass, or more preferably 5.0% by mass to 15.0% by mass.
[0231] The radical reaction initiator used for the cross-linking reaction is not particularly limited, and may be an inorganic peroxide, an organic peroxide, an azo compound, etc. These radical reaction initiators may also be combined.
[0232] The inorganic peroxide is not particularly limited, and examples include hydrogen peroxide, ammonium peroxide, potassium peroxide, sodium peroxide, and the like.
[0233] There are no particular limitations on the organic peroxide, and examples include benzoyl peroxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, α,α-bis(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, di-tert-hexyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxyhexyne-3, acetyl peroxide, isobutyryl peroxide, Capryl, decanoyl peroxide, lauroyl peroxide, 3,3,5-trimethylhexanoyl peroxide, m-toluoyl peroxide, tert-butyl peroxyisobutyrate, tert-butyl peroxyneodecanoate, cumyl peroxyneodecanoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, tert-butyl peroxybenzoate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxyacetate, etc.
[0234] The azo compound or diazo compound is not particularly limited, and examples include 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2,'-azobis-4-methoxy-2,4-dimethylvaleronitrile, azobisisobutyronitrile and the like.
[0235] Among them, organic peroxides are desirable because they are highly efficient and do not produce toxic byproducts such as cyanide compounds.
[0236] A free radical reaction initiator having a high hydrogen abstraction ability is desirable because the cross-linking reaction can be effectively carried out with a smaller amount of the initiator, and a free radical reaction initiator having a high hydrogen abstraction ability such as tert-butyl peroxyisopropyl monocarbonate, benzoyl peroxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, α,α-bis(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane or di-tert-hexyl peroxide is even more desirable.
[0237] The amount of the radical reaction initiator used is not particularly limited, but is preferably 0.1 to 50 parts by mass, or more preferably 0.2 to 5 parts by mass, relative to 100 parts by mass of the binder resin to be crosslinked.
[0238] The peak temperature of the endothermic peak of tetrahydrofuran (THF) insoluble matter other than the inorganic component in the toner measured using a differential scanning calorimeter (DSC) preferably occurs at 55° C. to 80° C., and the endothermic quantity ΔHt of the endothermic peak is preferably 3 J / g to 30 J / g. In the case where the endothermic quantity ΔHt of the endothermic peak falls within the above range, the winding resistance is further improved.
[0239] The endothermic heat amount ΔHt of the endothermic peak is more preferably 6 J / g to 30 J / g.
[0240] Examples of a method for adjusting the endothermic heat amount ΔHt of the endothermic peak within the above range include a method of adjusting the content of the monomer unit in the first resin or adjusting the content of the first resin in the binder resin.
[0241] In order to improve pigment dispersibility, the binder resin may contain a resin other than the first resin, the second resin, and the third resin as long as the advantageous effects of the present disclosure are not impaired.
[0242] Examples of such resins include those listed below.
[0243] Poly(vinyl chloride), phenolic resin, phenolic resin modified by natural resin, maleic acid resin modified by natural resin, poly(vinyl acetate) resin, silicone resin, polyester resin, polyurethane resin, polyamide resin, furan resin, epoxy resin, xylene resin, poly(vinyl butyral) resin, terpene resin, coumarone-indene resin and petroleum resin.
[0244] The toner particles may contain a colorant. Examples of the colorant include those listed below.
[0245] Examples of black colorants include carbon black, and materials toned to black by using yellow colorants, magenta colorants, and cyan colorants. The colorant may be a single pigment, but from the viewpoint of full-color image quality, it is preferred to use a colorant obtained by combining a dye and a pigment so as to improve clarity.
[0246] Examples of pigments for magenta toners include CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75 7:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, and 282; CI Pigment Violet 19; and CI Vat Red 1, 2, 10, 13, 15, 23, 29, and 35.
[0247] Examples of dyes for magenta toners include CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, and 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; oil-soluble dyes such as CI Disperse Violet 1, and CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, and 40; and basic dyes such as CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, and 28.
[0248] Examples of the pigment for cyan toner include CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, and 17; CI Vat Blue 6; and CI Acid Blue 45 and a copper phthalocyanine pigment having 1 to 5 phthalimidomethyl substituents in the phthalocyanine skeleton.
[0249] Examples of the dye for cyan toner include CI Solvent Blue 70.
[0250] Examples of the pigment for yellow toner include CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181 and 185; and CI Vat Yellow 1, 3 and 20.
[0251] Examples of the dye for yellow toner include CI Solvent Yellow 162.
[0252] The content of the colorant is preferably 0.1 to 30.0 parts by mass relative to 100 parts by mass of the binder resin.
[0253] The toner particles may contain wax. Examples of the wax include those listed below.
[0254] Microcrystalline wax, paraffin wax and Fischer-Tropsch wax; oxides of hydrocarbon waxes, such as oxidized polyethylene wax and block copolymers thereof; waxes mainly comprising fatty acid esters, such as carnauba wax; and waxes obtained by partially or completely deoxidizing fatty acid esters, such as deoxidized carnauba wax.
[0255] Further examples include the species listed below.
[0256] For example, saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brazic acid, eleostearic acid, and octadecatetraenoic acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, hexacosanol, and myricol; polyols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenyl alcohol, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnauba alcohol, hexacosanol, and myricol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; saturated Fatty acid bisamides; unsaturated fatty acid amides such as ethylenebis-oleamide, hexamethylenebis-oleamide, N,N'-dioleyl adipamide, and N,N'-dioleyl sebacic acid amide; aromatic bisamides such as meta-xylene bis-stearic acid amide and N,N'-distearylisophthalic acid amide; fatty metal salts (commonly referred to as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes obtained by grafting vinyl monomers such as styrene and acrylic acid onto aliphatic hydrocarbon waxes; partial esterification products of fatty acids and polyols such as monoglyceride of behenic acid; and methyl ester compounds having hydroxyl groups obtained by hydrogenation of vegetable fats and oils.
[0257] The content of the wax is preferably 2.0 to 30.0 parts by mass relative to 100 parts by mass of the binder resin.
[0258] It is preferred that a first peak and a second peak derived from the wax exist in the temperature difference distribution of the endothermic peak of the toner measured using differential scanning calorimetry. In addition, it is preferred that the peak top temperature of the first peak is at least 70° C., the second peak is adjacent to the first peak, the peak top temperature of the second peak is higher than the peak top temperature of the first peak, and the height of the valley between the first peak and the second peak is greater than 0 W / g. In this case, good characteristics can be achieved in terms of image scratch resistance.
[0259] The presence of a second peak adjacent to the first peak and having a peak top temperature higher than the peak top temperature of the first peak and the height of the valley between the first peak and the second peak being greater than 0 W / g means the presence of a wax showing affinity with the wax of the first peak but having a melting point different therefrom. In addition, because the peak top temperature of the second peak is higher than the peak top temperature of the first peak, the molecular weight of the wax of the second peak used together with the wax of the first peak is higher and is easily subjected to phase separation from the first resin which is a crystalline resin.
[0260] That is, because the wax of the second peak acts as a nucleating agent that causes phase separation, the wax of the first peak is also guided in a direction that causes phase separation from the first resin, which means that the exudation of the wax during fixing is better promoted. As a result, it is believed that the surface of the fixed image is covered with wax, thereby achieving excellent scratch resistance.
[0261] A toner having a first peak and a second peak derived from the waxes can be obtained by using a plurality of waxes having different melting points.
[0262] In addition, in order to make the height of the valley between the first peak and the second peak greater than 0 W / g, a wax having a similar composition or structure and having a portion where the peak temperature region overlaps when comparing the endothermic peaks of the individual waxes in DSC measurement can be used. For example, examples of hydrocarbon waxes include a combination of hydrocarbon waxes having different melting points, and a combination of polyethylene wax and polypropylene wax. Examples of ester waxes include a combination of ester waxes having different melting points.
[0263] From the viewpoint of further improving the scratch resistance of the image, the peak top temperature of the first peak is preferably at least 70° C., and more preferably at least 80° C. The peak top temperature of the second peak is preferably at least 80° C., and more preferably at least 90° C.
[0264] The toner particles may contain a charge control agent.
[0265] As the charge control agent, a known charge control agent can be used, but in particular, a metal compound of an aromatic carboxylic acid which is colorless, can increase the charging speed of the toner, and can stably maintain a constant charge amount is preferable.
[0266] Examples of negative charge control agents include salicylic acid metal compounds, naphthoic acid metal compounds, dicarboxylic acid metal compounds, polymer compounds having sulfonic acid or carboxylic acid on the side chain, polymer compounds having sulfonate or sulfonate compounds on the side chain, polymer compounds having carboxylate or carboxylate compounds on the side chain, boron compounds, urea compounds, silicon compounds, and calixarene. The charge control agent may be added to the toner particles from the inside or outside.
[0267] The content of the charge control agent is preferably 0.2 to 10.0 parts by mass relative to 100.0 parts by mass of the binder resin.
[0268] The toner may contain an external additive. For example, the toner may be obtained by externally adding an external additive to toner particles.
[0269] Inorganic fine particles such as silica fine particles, titanium oxide fine particles, and aluminum oxide fine particles are preferably used as the external additive.
[0270] It is preferred that the specific surface area be 50 to 400 m 2 / g of inorganic fine particles as an external additive for improving fluidity, and preferably has a specific surface area of 10 to 50 m 2 / g of inorganic particles to achieve long-term stability.
[0271] In order to improve both fluidity and durability, a combination of kinds of inorganic fine particles whose specific surface areas fall within the above range may be used.
[0272] The content of the external additive is preferably 0.1 to 10.0 parts by mass relative to 100 parts by mass of the toner particles. When the toner particles and the external additive are mixed, a well-known mixer such as a Henschel mixer may be used.
[0273] The toner may also be used as a single-component developer, but from the viewpoint of providing a stable image for a long period of time, it is preferred to use the toner as a two-component developer mixed with a magnetic carrier to further improve dot reproducibility. That is, a two-component developer containing a toner and a magnetic carrier is preferred, wherein the toner is the above-mentioned toner.
[0274] The magnetic carrier can be a commonly known carrier, such as iron powder or surface-oxidized iron powder; particles of metals such as iron, lithium, calcium, magnesium, nickel, ketone, zinc, cobalt, magnesium, chromium or rare earth elements, or particles of alloys or oxides of these metals; magnetic material such as ferrite; or a resin carrier (so-called resin carrier) in which a magnetic material is dispersed, which contains a magnetic material and a binder resin for keeping the magnetic material in a dispersed state.
[0275] In the case where the toner is used as a two-component developer mixed with a magnetic carrier, the content of the toner in the two-component developer is preferably 2% by mass to 15% by mass, and more preferably 4% by mass to 13% by mass.
[0276] There is no particular limitation on the production method of the toner particles, and a generally known production method such as a suspension polymerization method, an emulsion aggregation method, a melt kneading method, or a dissolution suspension method can be used.
[0277] A description will now be given using melt-kneading methods as examples, but the production method of toner particles is not limited to these.
[0278] First, in the raw material mixing step, a predetermined amount of the first resin and the second resin or a binder resin containing the first resin and the second resin is weighed, and other components such as wax, colorant and charge control agent as required as materials constituting toner particles are blended and mixed. Examples of the mixing device include a double cone mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer and a Mechano Hybrid (produced by Nippon Coke and Engineering Co., Ltd.).
[0279] Next, the mixed material is melt-kneaded so that other components are dispersed in the binder resin containing the first resin and the second resin. In the melt-kneading step, an intermittent kneading machine such as a pressure kneading machine or a Banbury mixer, or a continuous kneading machine can be used, and from the viewpoint of being able to produce continuously, single screw and twin screw extruders become mainstream. Examples thereof include KTK type twin screw extruder (produced by Kobe Steel Ltd.), TEM type twin screw extruder (produced by Toshiba Machine Co., Ltd.), PCM kneader (produced by Ikegai Corp.), twin screw extruder (produced by KCK Corp.), co-kneader (produced by Buss) and Kneadex (produced by Nippon Coke & Engineering Co., Ltd.). In addition, the resin composition obtained by melt-kneading is rolled using 2 rollers, and cooled by water or the like in the cooling step.
[0280] The dispersion state of the first resin and the second resin, the number average diameter of the domains, and the like can be controlled by adjusting the kneading temperature, the screw speed, and the like in the melt kneading step.
[0281] Next, the cooled resin composition is pulverized to a desired particle size in a pulverizing step. In the pulverizing step, the cooled resin composition can be coarsely pulverized using, for example, a pulverizer such as a crusher, a hammer mill, or a feather mill, and then finely pulverized using, for example, a Kryptron system (produced by Kawasaki Heavy Industries, Ltd.), a super rotor (produced by NisshinEngineering Inc.), a turbo grinder (produced by Turbo Kogyo), or a jet-type fine pulverizer.
[0282] Next, the toner particles can be obtained by classifying with the aid of a classifier or sifter such as an inertial classification type elbow ejector (produced by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (produced by Hosokawa Micron Corporation.), a TSP separator (produced by Hosokawa Micron Corporation.), or a Faculty (produced by Hosokawa Micron Corporation.), as required.
[0283] In addition, a description will now be given of the case where toner particles are produced using an emulsion aggregation method.
[0284] In the emulsion aggregation method, toner particles are produced through a dispersion step of preparing a fine particle dispersion liquid composed of the constituent materials of the colorant particles, an aggregation step of aggregating the fine particles composed of the constituent materials of the colorant particles and controlling the particle size until the particle size of the colorant particles is obtained, a fusion step of fusing the resin contained in the obtained aggregated particles, a subsequent cooling step, a metal removal step of filtering out the obtained colorant and removing excess polyvalent metal ions, a filtration and washing step of washing with ion exchange water or the like, and a step of removing moisture from the washed colorant particles and drying.
[0285] Preparation step of resin fine particle dispersion (dispersion step)
[0286] The resin fine particle dispersion can be prepared by a known method, but is not limited to these methods. Examples of the known method include an emulsion polymerization method, a self-emulsification method, a phase inversion emulsification method in which the resin is emulsified by adding an aqueous medium to a resin solution obtained by dissolving the resin in an organic solvent, and a forced emulsification method in which the resin is forcibly emulsified by a high temperature treatment in an aqueous medium without using an organic solvent.
[0287] Specifically, the first resin and the second resin are dissolved in an organic solvent in which these resins are dissolved, and a surfactant or an alkaline compound is added as needed. In such a case, if the resin is a crystalline resin having a melting point, the resin can be dissolved after heating the resin to a temperature above its melting point. Next, the fine resin particles are precipitated by slowly adding an aqueous medium while stirring with the aid of a homogenizer or the like. Then, the solvent is removed by heating or reducing pressure to prepare an aqueous dispersion of fine resin particles.
[0288] Any organic solvent that can dissolve the resin can be used as the organic solvent for dissolving the resin, but an organic solvent that forms a uniform phase with water, such as toluene, is preferred from the viewpoint of suppressing the generation of coarse powder.
[0289] There is no particular limitation on the type of surfactant, but examples thereof include anionic surfactants such as sulfate ester salts, sulfonates, carboxylates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols. One of these surfactants may be used alone, or a combination of at least two thereof may be used.
[0290] Examples of the basic compound include inorganic bases such as sodium hydroxide and potassium hydroxide, and organic bases such as ammonia, triethylamine, trimethylamine, dimethylaminoethanol, and diethylaminoethanol. One of these basic compounds may be used alone, or a combination of at least two thereof may be used.
[0291] In addition, the volume-based 50% particle diameter (D50) of the resin fine particles in the resin fine particle aqueous dispersion is preferably about 0.05 to 1.00 μm, and more preferably about 0.05 to 0.40 μm. By adjusting the volume-based 50% particle diameter (D50) within the above range, it is easy to obtain toner particles with a diameter of 3 to 10 μm, which is a suitable weight average particle diameter for toner particles.
[0292] In addition, the 50% particle diameter (D50) on a volume basis can be measured using a dynamic light scattering particle size distribution analyzer (Nanotrac UPA-EX150 manufactured by Nikkiso Co., Ltd.).
[0293] Preparation of colorant fine particle dispersion
[0294] The colorant fine particle dispersion liquid can be prepared by the publicly known methods listed below, but is not limited to these methods.
[0295] The colorant fine particle dispersion can be prepared by mixing the colorant, aqueous medium and dispersant using a mixer such as a known stirrer, emulsifier and disperser. The dispersant used here may be a known one such as a surfactant and a polymer dispersant.
[0296] Although any of the surfactant and the polymer dispersant may be removed in the washing step described below, the surfactant is preferred from the viewpoint of washing efficiency.
[0297] Examples of surfactants include anionic surfactants such as sulfate ester type, sulfonate type, carboxylate type, phosphate ester type, soap type, etc.; cationic surfactants such as amine salt type and quaternary ammonium salt type, etc.; and nonionic surfactants such as polyethylene glycol type, alkylphenol ethylene oxide adduct type, polyol type, etc.
[0298] Among them, nonionic surfactants and anionic surfactants are preferred. In addition, nonionic surfactants and anionic surfactants can be used together. Surfactants can be used alone or in combination of two or more thereof. The concentration of surfactant in the aqueous medium is preferably 0.5 mass % to 5 mass %.
[0299] The amount of the colorant fine particles in the colorant fine particle dispersion liquid is not particularly limited, but is preferably 1% by mass to 30% by mass relative to the total mass of the colorant fine particle dispersion liquid.
[0300] In addition, from the viewpoint of the dispersibility of the colorant in the toner particles finally obtained, the dispersed particle size of the colorant fine particles in the colorant fine particle aqueous dispersion is preferably such that the 50% particle size (D50) based on the volume distribution is 0.50 μm or less. In addition, for the same reason, it is preferred that the 90% particle size (D90) based on the volume distribution is 2 μm or less. The 50% particle size (D50) based on the volume distribution of the colorant particles dispersed in the aqueous medium can be measured by a dynamic light scattering type particle size distribution analyzer (NANOTRAC UPA-EX150: manufactured by Nikkiso Co., Ltd.).
[0301] Known mixers such as stirrers, emulsifiers, and dispersers for dispersing the colorant in an aqueous medium include ultrasonic homogenizers, jet mills, pressure homogenizers, colloid mills, ball mills, sand mills, and paint stirrers, which can be used alone or in combination.
[0302] Preparation of wax fine particle dispersion
[0303] The wax fine particle dispersion can be prepared using a known method given below, but is not limited to the known method.
[0304] The wax fine particle dispersion can be prepared by adding the wax to an aqueous medium containing a surfactant, heating to a temperature not lower than the melting point of the wax, dispersing in a particle state using a homogenizer having a strong shearing ability (e.g., "Clearmix W-Motion" produced by M Technique Co., Ltd.) or a pressure discharge type disperser (e.g., "Gaulin Homogenizer" produced by Gaulin), and then cooling to a temperature lower than the melting point of the wax.
[0305] In addition, the dispersed particle size of the wax fine particles in the wax fine particle dispersion is such that the volume-based 50% particle size (D50) is preferably about 0.03 to 1.0 μm, and more preferably about 0.10 to 0.50 μm. In addition, it is preferred that coarse wax particles having a diameter of at least 1 μm are absent.
[0306] If the dispersed particle size in the wax fine particle dispersion falls within the above range, the wax can be finely dispersed in the toner particles, the bleeding effect during fixing can be exerted to the greatest extent possible, and good separation can be achieved. In addition, a dynamic light scattering particle size distribution analyzer (Nanotrac UPA-EX150 produced by Nikkiso Co., Ltd.) can be used to measure the 50% particle size (D50) based on volume of the wax fine particle dispersion dispersed in the aqueous medium.
[0307] Mixing Steps
[0308] In the mixing step, a mixed solution is prepared by mixing the first resin fine particle dispersion, the second resin fine particle dispersion, and, if necessary, the wax fine particle dispersion, the colorant fine particle dispersion, etc. A known mixing device such as a homogenizer or a mixer can be used.
[0309] Aggregate particle formation step (aggregation step)
[0310] In the aggregation step, the fine particles contained in the mixed solution prepared in the mixing step are aggregated to form aggregates having a target particle size. Here, the aggregates are formed by aggregating the resin fine particles and the wax fine particles, the colorant fine particles, etc. as needed by adding and mixing an aggregating agent as needed and appropriately applying heat and / or mechanical force.
[0311] If necessary, an aggregating agent containing a divalent or higher-valent metal ion may be used as the aggregating agent.
[0312] Aggregating agents containing divalent or higher metal ions show high aggregation and can achieve desired targets even when added in small amounts. These aggregating agents can neutralize the ionic surfactant ions contained in the resin fine particle dispersion, wax fine particle dispersion, and colorant fine particle dispersion. As a result of salting out and ion crosslinking effects, resin fine particles, wax fine particles, and colorant fine particles are easily aggregated.
[0313] The aggregation step is a step of forming aggregates of toner particle size in an aqueous medium. The weight average particle size of the aggregates produced in the aggregation step is preferably 3 to 10 μm. In addition, the weight average particle size can be measured using a particle size distribution analyzer using the Coulter principle (Coulter Multisizer III: produced by Beckman Coulter, Inc.).
[0314] Fusion Steps
[0315] In the fusion step, an aggregation stopper may be added to the dispersion containing the aggregates obtained in the aggregation step while stirring in the same manner as in the aggregation step. Examples of the aggregation stopper include alkaline compounds that shift the balance of the acidic polar groups of the surfactant to the dissociation side and stabilize the aggregated particles. Other examples include chelating agents that partially dissociate the ionic crosslinking between the acidic polar groups in the surfactant and the metal ions as the aggregating agent and form a coordinate bond with the metal ions, thereby stabilizing the aggregated particles.
[0316] After the dispersion state of the aggregated particles in the dispersion liquid is stabilized due to the action of the aggregation stopper, the aggregated particles may be fused by heating the aggregated particles to a temperature not lower than the glass transition temperature or melting point of the binder resin.
[0317] The number average diameter of the domains can be controlled by adjusting the temperature in the fusing step.The weight average particle diameter of the obtained toner particles is preferably about 3 to 10 μm.
[0318] Filtration step, washing step, drying step and classification step
[0319] Next, toner particles can be obtained by subjecting the toner particle solid content to a filtering step, and, as necessary, a washing step, a drying step, and a classification step for adjusting the particle diameter.
[0320] The obtained toner particles can be used as toner as they are. The toner can be obtained by mixing the obtained toner particles with inorganic fine particles and other external additives as required. The toner particles, inorganic fine particles and other external additives can be mixed using a mixing device such as a double cone mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (produced by Nippon Coke and Engineering Co., Ltd.) or a Nobilta (produced by Hosokawa Micron Corporation.).
[0321] A description will now be given of methods of measuring various physical properties of the toner and raw materials.
[0322] Toner cross-sectional observation, domain-matrix structure, and measurement of number average diameter of domains
[0323] First, a thin sheet as a standard sample of the amount present is prepared.
[0324] The first resin as a crystalline resin was fully dispersed in a visible light curable resin (Aronix LCR series D800), and then cured by irradiation with short wavelength light. The obtained cured product was cut using an ultramicrotome equipped with a diamond knife to produce a thin slice sample with a size of 250 nm. A thin slice sample of a second resin as an amorphous resin was prepared in the same manner.
[0325] Next, kneaded products were prepared by mixing and melt-kneading the first resin and the second resin at mass ratios of 0 / 100, 30 / 70, 70 / 30 and 0 / 100. Then, in the same manner, sheet samples were produced by dispersing these kneaded products in a visible light curable resin, curing and cutting.
[0326] Next, the cross sections of these cut-out standard samples were observed using a transmission electron microscope (JEM-2800 electron microscope manufactured by JEOL Ltd.) (TEM-EDX), and element mapping was performed using EDX. The elements to be mapped were carbon, oxygen, and nitrogen.
[0327] The mapping conditions are as follows.
[0328] Accelerating voltage: 200 kV
[0329] Electron beam irradiation size: 1.5nm
[0330] Live time limit: 600 seconds
[0331] Dead time: 20 to 30
[0332] Mapping resolution: 256×256
[0333] Based on the spectral intensity of each element (average value of an area of 10 nm square), the values of (oxygen element intensity / carbon element intensity) and (nitrogen element intensity / carbon element intensity) are calculated, and a calibration curve is prepared for the mass ratio of the first resin and the second resin. In the case where the monomer unit in the first resin contains a nitrogen atom, the calibration curve of (nitrogen element intensity / carbon element intensity) is used for subsequent quantification. The toner sample is then analyzed.
[0334] The toner was sufficiently dispersed in a visible light curable resin (Aronix LCR series D800) and then cured by irradiation with short wavelength light. A thin sample having a size of 250 nm was produced by cutting the obtained cured product using an ultramicrotome equipped with a diamond knife.
[0335] Next, the cut sample was then observed using a transmission electron microscope (TEM-EDX) (JEM-2800 electron microscope produced by JEOL Ltd.) A cross-sectional image of the toner particles was obtained, and element mapping was performed using EDX. The elements to be mapped were carbon, oxygen, and nitrogen.
[0336] In addition, the toner cross section to be observed is selected in the following manner. First, the toner cross-sectional area is determined from the toner cross-sectional image, and the diameter of a circle having the same area as the cross-sectional area (equivalent circle diameter) is determined. Only toner cross-sectional images in which the absolute value of the difference between the equivalent circle diameter and the weight-average particle size (D4) of the toner is within 1.0 μm are used for observation.
[0337] For the domain confirmed by the observed image, the value of (oxygen element intensity / carbon element intensity) and / or (nitrogen element intensity / carbon element intensity) is calculated based on the spectral intensity of the element (average value of an area of 10 nm square), and the mass ratio of the first resin and the second resin is calculated by comparison with the above-mentioned calibration curve. A domain in which the ratio of the second resin is at least 80% is considered to be a domain in the present disclosure.
[0338] After identifying the domain confirmed by observing the image, the particle size of the domain present in the toner cross-sectional image is determined by binarization. The particle size is taken as the major axis of the domain. This is measured at 10 points per toner, and the arithmetic mean of the domain diameters of the 10 toners is taken as the number average diameter (μm) of the domain.
[0339] At the same time, the area of the domain is determined by adding the areas of all domains present in the toner cross-sectional image to obtain the total area, and this is represented by S1. This is measured at 10 points per toner, the total area of the domains in the 10 toners is calculated (i.e., S1+S2...+S100), and the arithmetic mean thereof is taken as the "domain area".
[0340] The toner cross-sectional area is determined by obtaining the total cross-sectional area of the toner determined from the toner cross-sectional image used when determining the domain area (10 dots per toner, and 10 toners), and the arithmetic mean thereof is taken as the "toner cross-sectional area". In addition, the value of [domain area] / [toner cross-sectional area]×100 is taken as the ratio of the domain area to the toner cross-sectional area (domain area ratio (%)).
[0341] In addition, binarization and number average diameter calculation were performed using Image Pro PLUS (manufactured by Nippon Roper KK).
[0342] Method for separating materials from toner
[0343] Each material contained in the toner can be separated from the toner by utilizing the difference in solubility of the materials in the solvent.
[0344] First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble matter (second resin) and the insoluble matter (first resin, wax, colorant, inorganic fine particles, etc.) are separated.
[0345] Second separation: The insoluble matter (first resin, wax, colorant, inorganic fine particles, etc.) obtained by the first separation is dissolved in MEK at 100°C, and the soluble matter (first resin, wax) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated.
[0346] Third separation: The soluble matter (first resin, wax) obtained by the second separation was dissolved in chloroform at 23°C, and the soluble matter (first resin) and the insoluble matter (wax) were separated.
[0347] Including the third resin
[0348] First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and soluble matters (second resin and third resin) and insoluble matters (first resin, wax, colorant, inorganic fine particles, etc.) are separated.
[0349] Second separation: The soluble matter (second resin and third resin) obtained by the first separation was dissolved in toluene at 23° C., and the soluble matter (third resin) and the insoluble matter (second resin) were separated.
[0350] Third separation: The insoluble matter (first resin, wax, colorant, inorganic fine particles, etc.) obtained by the first separation is dissolved in MEK at 100°C, and the soluble matter (first resin, wax) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated.
[0351] Fourth separation: The soluble matter (first resin, wax) obtained by the first separation was dissolved in chloroform at 23°C, and the soluble matter (first resin) and the insoluble matter (wax) were separated.
[0352] Measurement of Contents of First Resin and Second Resin in Binder Resin in Toner
[0353] The contents of the first resin and the second resin in the binder resin in the toner are calculated by measuring the mass of the soluble matter and the insoluble matter separated in the above separation step.
[0354] Identification method of monomer units constituting first, second and third resins and measurement method of content ratio
[0355] The identification method and content ratio measurement method of the monomer units constituting the first, second and third resins are determined by 1 H-NMR was carried out under the following conditions.
[0356] Measuring equipment: FT NMR equipment-JNM-EX400 (manufactured by JEOL Ltd.)
[0357] Measuring frequency: 400MHz
[0358] Pulse condition: 5.0μs
[0359] Frequency range: 10,500Hz
[0360] Cumulative times: 64 times
[0361] Measuring temperature: 30℃
[0362] Sample: 50 mg of the measurement sample was placed in a sample tube with an inner diameter of 5 mm, deuterated chloroform (CDCl3) was added as a solvent, and the measurement sample was dissolved in a constant temperature bath at 40°C. 1 In the H-NMR chart, from the peaks of the constituent elements attributed to the first monomer unit, a peak independent of the peaks of the constituent elements attributed to other monomer units is selected, and the integrated value S1 of the peak is calculated.
[0363] Similarly, from among the peaks attributable to the constituent element of the second monomer unit, a peak independent of the peaks attributable to the constituent elements of the other monomer units is selected, and the integrated value S2 of the peak is calculated.
[0364] Furthermore, when the third monomer unit is contained, a peak independent of peaks of constituent elements attributed to other monomer units is selected from the peaks of constituent elements attributed to the third monomer unit, and the integrated value S3 of the peak is calculated.
[0365] The content ratio of the first monomer unit is calculated in the following manner using the integrated values S1, S2, and S3. In addition, n1, n2, and n3 represent the number of hydrogen atoms in the constituent elements attributed to the peaks observed at the respective locations.
[0366] Content ratio of the first monomer unit (mol%) = {(S1 / n1) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100
[0367] Similarly, the content ratio of the second monomer unit and the third monomer unit is determined in the manner shown below.
[0368] Content ratio of the second monomer unit (mol%) = {(S2 / n2) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100
[0369] Content ratio of the third monomer unit (mol%) = {(S3 / n3) / ((S1 / n1)+(S2 / n2)+(S3 / n3))}×100
[0370] For example, in the case where a polymerizable monomer containing no hydrogen atom as a constituent element other than vinyl is used in the first, second, and third resins, 13 C as the measurement nucleus, in single pulse mode 13 C-NMR measurements and 1 The calculation was performed in the same manner as in the H-NMR measurement.
[0371] SP value calculation method
[0372] The SP value is determined in the following manner according to the calculation method proposed by Fedors.
[0373] For each polymerizable monomer, the evaporation energy (Δei) (cal / mol) and molar volume (Δvi) (cm2) of atoms and atomic groups in the molecular structure were determined from the table shown in "Polym. Eng. Sci., 14 (2), 147-154 (1974)". 3 / mol), and (4.184×ΣΔei / ΣΔvi) 0.5 Taken as SP value (J / cm 3 ) 0.5 .
[0374] For example, SP is calculated using a calculation method similar to the calculation method for atoms and atomic groups in the above-mentioned molecular structure in which the double bonds in the polymerizable monomer are broken by polymerization. 21 That is, SP can be determined by dividing the evaporation energy of the monomer unit by the molar volume. 21 The value of .
[0375] Method for measuring weight average molecular weight (Mw) of resin etc. using gel permeation chromatography (GPC)
[0376] The weight average molecular weight (Mw) of tetrahydrofuran (THF)-soluble matter in the resin or the like is measured using gel permeation chromatography (GPC) in the following manner.
[0377] First, the resin and the like are dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The obtained solution is then filtered using a solvent-resistant membrane filter ("Mishoridisk" (pretreatment disk) produced by Tosoh Corporation) having a pore size of 0.2 μm to obtain a sample solution. In addition, the sample solution is prepared so that the concentration of the THF soluble component is about 0.8% by mass. The sample solution is used for measurement under the following conditions.
[0378] Equipment: HLC8120 GPC (detector: RI) (manufactured by Tosoh Corporation)
[0379] Column: Combination of Shodex KF-801, 802, 803, 804, 805, 806 and 807 (manufactured by Showa Denko KK)
[0380] Eluent: Tetrahydrofuran (THF)
[0381] Flow rate: 1.0mL / min
[0382] Oven temperature: 40.0℃
[0383] Injection volume: 0.10mL
[0384] When calculating the molecular weight of a sample, a molecular weight calibration curve is prepared using standard polystyrene resins (trade names "TSK standard polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000 and A-500", produced by Tosoh Corporation).
[0385] Method for measuring melting point, endothermic peak and endothermic quantity of toner and resin, etc. and peak temperature of wax in temperature difference distribution
[0386] The melting points and the endothermic peaks and endothermic quantities of the toner, resin, and the like are measured using DSC Q1000 (manufactured by TA Instruments) under the following conditions.
[0387] Heating rate: 10℃ / min
[0388] Measurement start temperature: 20°C
[0389] Measurement end temperature: 180℃
[0390] The melting points of indium and zinc were used for temperature calibration of the detectors in the device, and the heat of fusion of indium was used for thermal calibration.
[0391] Specifically, about 5 mg of the sample was weighed out, put into an aluminum pan, and subjected to differential scanning calorimetry. A blank silver pan was used as a reference.
[0392] The melting point is taken as the peak temperature of the maximum endothermic peak in the first temperature increasing step.
[0393] In addition, when there are multiple peaks, the maximum endothermic peak is taken as the peak with the largest endothermic amount. In addition, the endothermic amount of the maximum endothermic peak is determined.
[0394] When the toner is used as a sample, the peak top temperatures of the first peak and the second peak derived from the wax are calculated from the temperature-endothermic quantity curve differentiated with respect to temperature in the temperature range of 30° C. to 140° C. In addition, the height of the valley between the first peak and the second peak is also calculated.
[0395] Confirmation of whether the first and second peaks are derived from wax
[0396] By confirming the peak top temperature in the temperature difference distribution of the endothermic peak measured by DSC of the insoluble matter (wax) obtained using the above separation method, it can be determined whether the first peak and the second peak are derived from the wax.
[0397] In addition, tetrahydrofuran (THF)-insoluble matter other than the inorganic component in the toner can be prepared in the following manner.
[0398] Method for measuring tetrahydrofuran (THF) insoluble matter other than inorganic components in toner
[0399] 1.5 g of toner (0.7 g in the case of measuring THF insoluble matter in a single resin) (W1 g) for measuring THF insoluble matter was accurately weighed and placed in a cylindrical filter paper (trade name: No.86R, size: 28×100 mm, produced by Advantec Toyo Kaisha, Ltd.) that had been accurately weighed in advance, and then placed in a Soxhlet extraction apparatus. Extraction was performed for 18 hours using 200 mL of tetrahydrofuran (THF) as a solvent, and the extraction was performed at a reflux rate such that the solvent extraction cycle lasted for about five minutes.
[0400] After the extraction was completed, the cylindrical filter paper was taken out, air-dried, and then vacuum-dried at 40°C for eight hours, after which the mass of the cylindrical filter paper including the extraction residue was weighed, and the mass of the extraction residue was calculated by subtracting the mass of the cylindrical filter paper (W2g).
[0401] Next, the content (W3 g) of the inorganic component was determined using the following procedure (in the case of measuring the THF-insoluble matter in a single resin, the value of W3 was taken as 0 g).
[0402] About 2 g of toner (Wag) is accurately weighed into a 30 mL magnetic crucible that has been accurately weighed in advance.
[0403] The magnetic crucible is placed in an electric furnace and heated at a temperature of about 900°C for about three hours, gradually cooled in the electric furnace, and then gradually cooled in a dryer at room temperature for at least one hour, after which the mass of the crucible including the incineration ash is accurately weighed, and the incineration ash content (Wbg) is calculated by subtracting the mass of the crucible.
[0404] Next, the content (W3g) of the incineration ash in the W1g sample was calculated using the following formula (A).
[0405] W3=W1×(Wb / Wa) (A)
[0406] In this case, the amount of THF-insoluble matter was determined using the following formula (B).
[0407] THF insoluble matter (mass %) = {(W2-W3) / (W1-W3)}×100 (B)
[0408] In addition, the THF-soluble matter can be recovered by sufficiently distilling off THF from the THF-soluble component using an evaporator.
[0409] Acid value measurement method
[0410] The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. The acid value is measured in accordance with JIS K0070-1992, but is specifically measured using the following operation.
[0411] (1) Preparation of reagents
[0412] A phenolphthalein solution was obtained by dissolving 1.0 g of phenolphthalein in 90 mL of ethanol (95% by volume) and adding ion-exchanged water until the volume was 100 mL.
[0413] 7g of special grade potassium hydroxide is dissolved in 5mL water, and ethanol (95% by volume) is added until the volume is 1L. Potassium hydroxide solution is obtained by placing the obtained solution in an alkali-resistant container so as not to contact with carbon dioxide gas, etc., allowing the solution to stand for three days, and then filtering. The potassium hydroxide solution obtained is stored in an alkali-resistant container. The factor of potassium hydroxide solution is determined as follows: 25mL of 0.1mol / L hydrochloric acid is placed in a conical flask, a few drops of phenolphthalein solution are added, titrated with potassium hydroxide solution, and the factor is determined by the amount of potassium hydroxide solution required for neutralization. 0.1mol / L hydrochloric acid is prepared according to JIS K 8001-1998.
[0414] (2) Operation
[0415] (A) Main test
[0416] In 200mL conical flask, accurately measure 2.0g of pulverized sample, add the mixed solution of 100mL toluene / ethanol (2:1), and dissolve sample five hours.Next, add a few drops of phenolphthalein solution as indicator, and use potassium hydroxide solution to titrate.In addition, think that the endpoint of titration is the point when the light red of indicator lasts about 30 seconds.
[0417] (B) Blank test
[0418] Titration was performed in the same manner as in the above operation, except that no sample was used (ie, only a mixed solution of toluene / ethanol (2:1) was used).
[0419] (3) The acid value is calculated by substituting the obtained result into the following formula.
[0420] A=[(CB)×f×5.61] / S
[0421] Here, A represents the acid value (mgKOH / g), B represents the amount of potassium hydroxide solution added in the blank test (mL), C represents the amount of potassium hydroxide solution added in the main test (mL), f represents the factor of the potassium hydroxide solution, and S represents the mass of the sample (g).
[0422] Method for measuring hydroxyl value
[0423] The hydroxyl value is the number of milligrams of potassium hydroxide required to neutralize acetic acid bonded to a hydroxyl group when 1 g of a sample is acetylated. The hydroxyl value is measured in accordance with JIS K 0070-1992, but is specifically measured using the following operation.
[0424] (1) Preparation of reagents
[0425] The acetylating agent was obtained by placing 25 g of special grade acetic anhydride in a 100 mL volumetric flask, adding pyridine until the total amount was 100 mL, and shaking well. The obtained acetylating agent was stored in a brown bottle so as not to come into contact with moisture, carbon dioxide gas, etc.
[0426] A phenolphthalein solution was obtained by dissolving 1.0 g of phenolphthalein in 90 mL of ethanol (95% by volume) and adding ion-exchanged water until the volume was 100 mL.
[0427] 35g of special grade potassium hydroxide is dissolved in 20mL water, and ethanol (95 volume %) is added until the volume is 1L. Potassium hydroxide solution is obtained by putting the solution obtained into an alkali-resistant container so as not to contact with carbon dioxide gas etc., leaving the solution to stand for three days, and then filtering. The potassium hydroxide solution obtained is stored in an alkali-resistant container. The factor of potassium hydroxide solution is determined as follows: 25mL of 0.5mol / L hydrochloric acid is put into a conical flask, a few drops of phenolphthalein solution are added, titrated with potassium hydroxide solution, and the factor is determined by the amount of potassium hydroxide solution required for neutralization. 0.5mol / L hydrochloric acid is made according to JIS K 8001-1998.
[0428] (2) Operation
[0429] (A) Main test
[0430] 1.0 g of the pulverized sample was accurately weighed into a 200 mL round bottom flask, and 5.0 mL of the acetylating agent was accurately added to the flask using a pipette. If the sample was difficult to dissolve in the acetylating agent during this process, dissolution was achieved by adding a small amount of special grade toluene.
[0431] A small funnel is placed on the mouth of the flask, and the flask is heated by immersing about 1 cm of the bottom in a glycerol bath at about 97° C. At this time, it is preferred to cover the base of the neck of the flask with thick paper having a round hole therein in order to prevent the temperature of the neck of the flask from rising by the heat from the bath.
[0432] After one hour, the flask was taken out from the glycerol bath and cooled. After cooling, 1 mL of water was added from the funnel, and then the flask was shaken to hydrolyze the acetic anhydride. In order to achieve complete hydrolysis, the flask was heated again for 10 minutes using a glycerol bath. After the flask was cooled, the funnel and flask walls were washed with 5 mL of ethanol.
[0433] A few drops of phenolphthalein solution are added as an indicator, and titration is performed using potassium hydroxide solution. In addition, the endpoint of the titration is considered to be the point when the light red color of the indicator lasts for about 30 seconds.
[0434] (B) Blank test
[0435] The titration was performed using a similar procedure as above, except that no sample was used.
[0436] (3) The hydroxyl value is calculated by substituting the obtained result into the following formula.
[0437] A=[{(BC)×28.05×f} / S]+D
[0438] Here, A represents the hydroxyl value (mgKOH / g), B represents the amount of potassium hydroxide solution added in the blank test (mL), C represents the amount of potassium hydroxide solution added in the main test (mL), f represents the factor of the potassium hydroxide solution, S represents the mass of the sample (g), and D represents the acid value of the sample (mgKOH / g),
[0439] Measurement method of resin softening point (Tm)
[0440] The softening point of the resin was measured using a constant load extrusion type capillary rheometer "Flow Tester CFT-500D flow property analyzer" (produced by Shimadzu Corporation), wherein the measurement was performed according to the manual attached to the apparatus. In this apparatus, while a constant load is applied from above the measurement sample by means of a piston, the measurement sample filled in the cylinder is heated up, thereby melting the sample, the molten measurement sample is extruded through a die at the bottom of the piston, and a flow curve can be obtained from the movement amount and temperature of the piston during this process.
[0441] In addition, the softening temperature is taken as the "melting temperature of the 1 / 2 method" described in the manual attached to the "Flow Tester CFT-500D flow characteristics analyzer." In addition, the melting temperature in the 1 / 2 method is calculated as follows.
[0442] First, half of the difference between the amount of movement of the piston at the end of outflow (outflow end point; represented by Smax) and the amount of movement of the piston at the start of outflow (lowest point; represented by Smin) is obtained (this is designated as X. X = (Smax-Smin) / 2). Next, the temperature in the flow curve when the amount of movement of the piston reaches the sum of X and Smin is taken as the melting temperature of the 1 / 2 method.
[0443] A measurement sample is prepared using a tablet molding press (eg, Standard Manual Newton Press NT-100H manufactured by NPa System Co., Ltd.) by compression molding about 1.0 g of the resin at about 10 MPa in an environment of 25° C. for about 60 seconds to provide a cylindrical shape having a diameter of about 8 mm.
[0444] Perform specific measurement operations according to the manual included with the equipment.
[0445] The measurement conditions of Flow Tester CFT-500D are as follows.
[0446] Test mode: Heating method
[0447] Starting temperature: 50℃
[0448] End point temperature: 200℃
[0449] Measuring interval: 1.0℃
[0450] Heating rate: 4.0℃ / min
[0451] Piston cross-sectional area: 1.000cm 2
[0452] Test load (piston load): 10.0kgf (0.9807MPa)
[0453] Warm-up time: 300 seconds
[0454] Die hole diameter: 1.0mm
[0455] Mold length: 1.0mm
[0456] Method for measuring weight average particle size (D4) of toner (particles)
[0457] The weight average particle diameter (D4) of the toner (particles) is calculated by measuring using a precision particle size distribution measuring device ("Coulter Counter Multisizer 3" registered trademark produced by Beckman Coulter, Inc.) which adopts a pore resistance method and uses a 100 μm aperture tube and attached dedicated software ("Beckman Coulter Multisizer 3 Version 3.51" produced by Beckman Coulter, Inc.) for setting measurement conditions and analyzing measurement data (the number of effective measurement channels: 25,000), and then analyzing the measurement data.
[0458] A solution obtained by dissolving special grade sodium chloride at a concentration of about 1% by mass in ion exchange water, such as "ISOTON II" (produced by Beckman Coulter, Inc.), can be used as the aqueous electrolytic solution used in the measurement.
[0459] In addition, before performing measurement and analysis, the dedicated software was set as follows.
[0460] On the "Standard Operating Method (SOM) Modification Screen" in the dedicated software, set the total count in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to "Standard Particles 10.0 μm" (Beckman Coulter, Inc.). The threshold and noise level are automatically set by pressing the Threshold / Noise Level Measurement button. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the "Rinse Orifice Tube After Measurement" option.
[0461] On the "Pulse to Size Conversion Screen" in the dedicated software, set the element spacing to logarithmic size, the size elements to 256 size elements, and the size range to 2 μm to 60 μm.
[0462] The specific measurement method is as follows.
[0463] (1) Place 200 mL of the electrolytic aqueous solution in a 250 mL glass round-bottom beaker dedicated to the Multisizer 3, place the beaker on the sample stage, and rotate the stirring rod counterclockwise at a rate of 24 rpm. Remove dirt and bubbles in the nozzle by using the "swept nozzle flushing" function of the dedicated software.
[0464] (2) 30 mL of the electrolytic aqueous solution was placed in a 100 mL glass flat-bottom beaker, and approximately 0.3 mL of a dilution obtained by diluting "Contaminon N" (a 10 mass % aqueous solution of a neutral detergent having a pH of 7 for cleaning precision measuring instruments and containing a nonionic surfactant, anionic surfactant, and an organic builder, produced by Wako Pure Chemical Industries, Ltd.) by 3 mass times with ion-exchanged water was added to the beaker as a dispersant.
[0465] (3) A predetermined amount of ion exchange water was placed in a water bath of "Ultrasonic Dispersion System Tetora 150" (manufactured by Nikkaki Bios Co., Ltd.) equipped with two oscillators with an oscillation frequency of 50 kHz so that their phases were shifted by 180° and an electric power output of 120 W, and about 2 mL of Contaminon N was added to the water bath.
[0466] (4) Place the beaker mentioned in the above section (2) into the beaker fixing hole of the ultrasonic disperser and start the ultrasonic disperser. Adjust the height of the beaker so that the resonance state of the liquid surface of the electrolytic aqueous solution in the beaker is the maximum.
[0467] (5) While irradiating the electrolytic aqueous solution in the beaker mentioned in the above section (4) with ultrasonic waves, about 10 mg of the toner (particles) is added to the electrolytic aqueous solution in small amounts at a time and dispersed therein. The ultrasonic dispersion treatment is continued for another 60 seconds. In addition, when performing ultrasonic dispersion, the temperature of the water bath is appropriately adjusted to a temperature of 10° C. to 40° C.
[0468] (6) The electrolytic aqueous solution in which the toner (particles) is dispersed as mentioned in the above section (5) is added dropwise by means of a pipette to the round-bottomed beaker set on the sample stage as mentioned in the above section (1), and the measurement concentration is adjusted to about 5%. The measurement is performed until the number of particles measured reaches 50,000.
[0469] (7) The weight average particle size (D4) is calculated by analyzing the measurement data using the attached dedicated software. In addition, when the chart / volume % is set with the dedicated software, the "average diameter" on the analysis / volume statistics (arithmetic mean) screen is the weight average particle size (D4).
[0470] Measuring method of 50% particle diameter (D50) based on volume of resin fine particles, wax fine particles and colorant fine particles
[0471] A dynamic light scattering particle size distribution analyzer (Nanotrac UPA-EX150 manufactured by Nikkiso Co., Ltd.) is used to measure the volume-based 50% particle size (D50) of the fine particles. Specifically, the measurement is performed using the following procedure.
[0472] In order to prevent aggregation of the measurement sample, a dispersion obtained by dispersing the measurement sample in an aqueous solution containing Family Fresh (produced by Kao Corporation) was put in and stirred. After stirring, the measurement sample was injected into the device, and then two measurements were performed, and the average value was determined.
[0473] As for the measurement conditions, the measurement time was 30 seconds, the refractive index of the sample particles was 1.49, the dispersion medium was water, and the refractive index of the dispersion medium was 1.33.
[0474] The volume particle size distribution of the measurement sample is measured, and from the measurement result, the particle size at which the cumulative value from the small particle size side in the volume particle size distribution reaches 50% is taken as the volume-based 50% particle size (D50) of the fine particles.
[0475] Example
[0476] The present disclosure will now be described in more detail using the examples given below. However, these examples are by no means limiting the present disclosure. Unless otherwise stated, in the following formulations, "parts" always mean parts by mass.
[0477] Production Example of First Resin 1 (Crystalline Resin 1)
[0478]
[0479] [tert-Butyl peroxypivalate (Perbutyl PV, produced by NOF Corp.)]
[0480] In a nitrogen atmosphere, the above-listed materials were placed in a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer and a nitrogen inlet tube. While stirring at 200 rpm, the contents of the reaction vessel were heated to 70° C. and subjected to polymerization for 12 hours, thereby obtaining a solution in which the polymer of the monomer composition was dissolved in toluene.
[0481] The solution was then cooled to 25°C, and the solution was put into 1000.0 parts of methanol under stirring, thereby causing precipitation of methanol-insoluble matter. The methanol-insoluble matter thus obtained was filtered and washed with methanol, and then vacuum dried at 40°C for 24 hours, thereby obtaining the first resin 1 (crystalline resin 1). The first resin 1 (crystalline resin 1) had a weight average molecular weight (Mw) of 34,000, a melting point (Tp) of 61°C, an acid value of 20.0 mgKOH / g, and a hydroxyl value of 0.0 mgKOH / g.
[0482] When NMR analysis was performed, the first resin 1 (crystalline resin 1) contained 20.0 mol% of monomer units derived from behenyl acrylate, 30.9 mol% of monomer units derived from acrylonitrile, 5.7 mol% of monomer units derived from acrylic acid, and 43.4 mol% of monomer units derived from styrene. In addition, the SP value (unit: (J / cm 3 ) 0.5 ).
[0483] Production Example of First Resins 2 to 23 (Crystalline Resins 2 to 23)
[0484] First resins 2 to 23 (crystalline resins 2 to 23) were obtained by performing reactions similar to those used in the production example of first resin 1 (crystalline resin 1), except that the monomers and mass fractions were changed as shown in Table 1. The results are shown in Tables 2 and 3.
[0485] [Table 1]
[0486]
[0487] [Table 2]
[0488]
[0489] SP in the table 11 , SP 21 and SP 31 The unit is (J / cm3 ) 0.5 .
[0490] The abbreviations used in Tables 1 and 2 are as follows.
[0491] BEA: Behenyl Acrylate
[0492] SA: Stearyl acrylate
[0493] MYA: Triacontyl acrylate
[0494] HA: Hexadecyl acrylate
[0495] AN: Acrylonitrile
[0496] HPMA: 2-Hydroxypropyl Methacrylate
[0497] AA: Acrylic acid
[0498] VA: Vinyl acetate
[0499] St:Styrene
[0500] MMA: Methyl Methacrylate
[0501] [Table 3]
[0502]
[0503] Production Example of Second Resin 1 (Amorphous Resin 1)
[0504] 50.0 parts of xylene were placed in an autoclave, and then replaced with nitrogen, and thereafter the temperature of the autoclave was raised to 185° C. in a sealed state with stirring.
[0505] While the temperature in the autoclave was controlled at 185° C., a mixed solution of 79.0 parts of styrene, 17.0 parts of n-butyl acrylate, 3.1 parts of divinylbenzene, 0.9 parts of acrylic acid, 1.0 part of di-tert-butyl peroxide and 20.0 parts of xylene was continuously dropped for three hours and polymerized.
[0506] The temperature was further maintained for one hour to complete the polymerization and remove the solvent to obtain a second resin 1 (amorphous resin 1). The second resin 1 (amorphous resin 1) had a weight average molecular weight (Mw) of 60,000, a softening point (Tm) of 140°C, an acid value of 15.0 mgKOH / g, and a hydroxyl value of 0.0 mgKOH / g.
[0507] Production Example of Second Resins 2 to 16 and 20 to 22 (Amorphous Resins 2 to 16 and 20 to 22)
[0508] Second resins 2 to 16 and 20 to 22 (amorphous resins 2 to 16 and 20 to 22) were obtained by performing a reaction similar to that used in the production example of second resin 1 (amorphous resin 1), except that the monomers and mass fractions were changed in the manner shown in Table 4. The physical properties are shown in Table 5.
[0509] Production Example of Second Resin 17 (Amorphous Resin 17)
[0510] Formula of polyester resin 1
[0511]
[0512] 90 parts of the mixture of monomers for producing polyester resin 1 was put into a four-necked flask, a decompression device, a water separation device, a nitrogen introduction device, a temperature measurement device and a stirring device were attached to the flask, and stirring was performed at 160° C. in a nitrogen atmosphere.
[0513] Next, 10 parts of vinyl polymerizable monomers for producing a vinyl resin (81.0 parts of styrene, 17.0 parts of n-butyl acrylate, 0.9 parts of acrylic acid and 1.1 parts of divinylbenzene) and 1 part of benzoyl peroxide as a polymerization initiator were dropped from a dropping funnel for four hours, and a reaction was performed at 160° C. for five hours.
[0514] Then the temperature was raised to 230° C., tetrabutoxytitanium was added in an amount of 0.2 parts relative to the total amount of monomers for producing the polyester resin, and polymerization was performed until a softening point of 115° C. was reached. After the reaction was completed, the polymer was taken out from the container, cooled, and pulverized to obtain a second resin 17 (amorphous resin 17). The physical properties are shown in Table 5.
[0515] Production Example of Second Resin 18 (Amorphous Resin 18)
[0516] Second resin 18 (amorphous resin 18) was obtained by performing a reaction similar to that used in the production example of second resin 17 (amorphous resin 17), except that the number of parts of the monomer mixture used to produce polyester resin 1 was changed from 90 parts to 80 parts, and the number of parts of the vinyl polymerizable monomer used to produce the vinyl resin was changed from 10 parts to 20 parts. The physical properties are shown in Table 5.
[0517] Production Example of Second Resin 19 (Amorphous Resin 19)
[0518] Second resin 19 (amorphous resin 19) was obtained by performing a reaction similar to that used in the production example of second resin 17 (amorphous resin 17), except that the number of parts of the monomer mixture used to produce polyester resin 1 was changed from 90 parts to 40 parts, and the number of parts of the vinyl polymerizable monomer used to produce the vinyl resin was changed from 10 parts to 60 parts. The physical properties are shown in Table 5.
[0519] [Table 4]
[0520]
[0521] The abbreviations used in Table 4 are as follows.
[0522] St:Styrene
[0523] MMA: Methyl Methacrylate
[0524] BA: n-butyl acrylate
[0525] OA: n-octyl acrylate
[0526] DVB: divinylbenzene
[0527] DDA: Lauryl acrylate
[0528] HPMA: 2-Hydroxypropyl Methacrylate
[0529] AA: Acrylic acid
[0530] [Table 5]
[0531]
[0532] Production Example of Binder Resin 1
[0533] ·First resin 1 60 parts
[0534] Second resin 1 40 parts
[0535] The components listed above were mixed and fed to a twin-screw mixer (S5KRC kneader manufactured by Kurimoto, Ltd.) at a rate of 1 kg / h, and 4.0 parts of tert-butyl peroxyisopropyl monocarbonate as a radical reaction initiator were fed at a rate of 0.1 kg / h at the same time. The reaction was carried out while kneading and extruding at 160° C. and 100 rpm for five minutes.
[0536] Next, nitrogen was supplied from the exhaust port and mixed while removing the organic solvent. The obtained kneaded product was cooled to obtain a binder resin 1. By measuring using gel permeation chromatography (GPC), it was confirmed that the first resin 1 and the second resin 1 partially reacted and the weight average molecular weight increased. The content of the third resin in the binder resin 1 was 5% by mass.
[0537] Production Example of Binder Resins 2 and 3
[0538] Binder resin 2 was obtained by producing in the same manner as in the production example of binder resin 1, except that first resin 2 was used instead of first resin 1.
[0539] The binder resin 3 is obtained in the same manner except that the first resin 3 is used instead of the first resin 1 .
[0540] By measurement using GPC, it was confirmed that in the binder resin 2, the first resin 2 and the second resin 1 partially reacted and the molecular weight increased. The content of the third resin in the binder resin 2 was 5% by mass. It was confirmed that in the binder resin 3, the first resin 3 and the second resin 1 partially reacted and the molecular weight increased. The content of the third resin in the binder resin 3 was 5% by mass.
[0541] Production Example of Binder Resin 4
[0542] Binder resin 4 was obtained by producing in the same manner as in the production example of binder resin 3 except that the mass parts of the radical reaction initiator was changed from 4.0 parts to 3.0 parts.
[0543] By measurement using GPC, it was confirmed that the first resin 3 and the second resin 1 partially reacted and the molecular weight increased. The content of the third resin in the binder resin 4 was 3% by mass.
[0544] Production Example of Binder Resin 5
[0545] Binder resin 5 was obtained by producing in the same manner as in the production example of binder resin 3 except that the mass fraction of the radical reaction initiator was changed from 4.0 parts to 1.0 part.
[0546] By measurement using GPC, it was confirmed that the first resin 3 and the second resin 1 partially reacted and the molecular weight increased. The content of the third resin in the binder resin 5 was 1% by mass.
[0547] Production Example of Binder Resin 6
[0548] Binder resin 6 was obtained by production in the same manner as in the production example of binder resin 3 except that the resin supply rate was changed from 1.0 kg / h to 0.5 kg / h.
[0549] By measurement using GPC, it was confirmed that the first resin 3 and the second resin 1 partially reacted and the molecular weight increased. The content of the third resin in the binder resin 6 was 2% by mass.
[0550] Production Example of Binder Resin 7
[0551] Binder resin 7 was obtained by producing in the same manner as in the production example of binder resin 6 except that the mass parts of the radical reaction initiator was changed from 4.0 parts to 8.0 parts.
[0552] By measurement using GPC, it was confirmed that the first resin 3 and the second resin 1 partially reacted and the molecular weight increased. The content of the third resin in the binder resin 7 was 4% by mass.
[0553] Production Example of Binder Resin 8
[0554] Binder resin 7 was obtained by producing in the same manner as in the production example of binder resin 6 except that the mass fraction of the radical reaction initiator was changed from 4.0 parts to 12.0 parts. By using GPC measurement, it was confirmed that the first resin 3 and the second resin 1 partially reacted and the molecular weight increased. The content of the third resin in the binder resin 8 was 8% by mass.
[0555] Production Example of Toner Particles 1
[0556] ·Binder resin 1 100 parts
[0557] · Hydrocarbon wax 5.0 parts
[0558] (Fischer-Tropsch wax; peak temperature of maximum endothermic peak in DSC: 90°C)
[0559] ·CI Pigment Blue 15:3 6.5 parts
[0560] Using a Henschel mixer (FM-75 model, manufactured by Nippon Coke and Engineering Co., Ltd.), the mixture was stirred for 20 s. -1 The above-listed materials were mixed for five minutes at a rotation speed of 250 rpm and then kneaded using a twin-screw mixer (PCM-30 type, produced by Ikegai Corp) with a temperature setting of 130° C. at a screw speed of 250 rpm and a discharge temperature of 130° C. The kneaded product obtained was cooled and then coarsely pulverized to a size of not more than 1 mm using a hammer mill to obtain a coarsely pulverized product. The coarsely pulverized product obtained was then finely pulverized using a mechanical pulverizer (T-250, produced by Freund Turbo Corporation).
[0561] The finely pulverized product was then classified by using Faculty F-300 (manufactured by Hosokawa Micron Corporation.) to obtain toner particles 1 having a weight average particle size of 6.0 μm. The operating conditions were a rotation speed of the classifying rotor of 130 s -1 and the speed of the dispersion rotor is 120s -1 .
[0562] Production Examples of Toner Particles 2 to 41 and 43 to 66
[0563] In addition to the resin used, its addition amount, mixing temperature, and screw speed (shown in the table as rpm) -1 ) was changed as shown in Tables 6-1 to 6-3 (for example, for toner particle 9, 60 parts of crystalline resin 1 and 40 parts of non-crystalline resin 1 were used instead of binder resin 1), and toner particles 2 to 41 and 43 to 66 were obtained by production in the same manner as in the production example of toner particle 1. In addition, the production method "1" in the production conditions in the table means "melt kneading method", and the production method "2" means "emulsion aggregation method".
[0564] [Table 6-1]
[0565]
[0566] [Table 6-2]
[0567]
[0568] [Table 6-3]
[0569]
[0570] Wax 1: Fischer-Tropsch wax; peak temperature of maximum endothermic peak in DSC: 90°C
[0571] Wax 2: Fischer-Tropsch wax; peak temperature of maximum endothermic peak in DSC: 105°C
[0572] Wax 3: petroleum wax; peak temperature of maximum endothermic peak in DSC: 78°C
[0573] Production Example of Crystalline Resin 3 Fine Particle Dispersion Liquid
[0574] Toluene (produced by Wako Pure Chemical Industries, Ltd.) 300 parts
[0575] Crystalline resin 3 100 parts
[0576] The materials listed above were weighed out, mixed and dissolved at 90°C.
[0577] 5.0 parts of sodium laurylbenzenesulfonate and 10.0 parts of sodium laurate were added to 700 parts of ion exchange water, respectively, and dissolved by heating at 90°C. Next, the toluene solution and the above aqueous solution were mixed together and stirred at 7000rpm using a TKRobomix ultra-high speed stirrer (produced by Primix Corporation). The obtained mixture was then emulsified under a pressure of 200MPa using a Nanomizer high pressure impact disperser (produced by Yoshida Kikai Co., Ltd.). Then, an aqueous dispersion (crystalline resin 3 fine particle dispersion) containing crystalline resin 3 fine particles at a concentration of 20% by mass was obtained by removing toluene using an evaporator and adjusting the concentration using ion exchange water.
[0578] The 50% particle diameter (D50) by volume of the crystalline resin fine particles 3 was measured using a dynamic light scattering particle size distribution analyzer (Nanotrac UPA-EX150 manufactured by Nikkiso Co., Ltd.) and found to be 0.40 μm.
[0579] Production Example of Amorphous Resin 6 Fine Particle Dispersion Liquid
[0580] Tetrahydrofuran (produced by Wako Pure Chemical Industries, Ltd.) 300 parts
[0581] ·Amorphous resin 6 100 parts
[0582] Anionic surfactant (Neogen RK manufactured by DKS Co., Ltd.) 0.5 parts
[0583] The materials listed above were weighed out, mixed and dissolved.
[0584] Next, 20.0 parts of 1 mol / L ammonia water were added and stirred at 4000 rpm using a TK Robomix ultra-high speed stirrer (produced by Primix Corporation). 700 parts of ion exchange water were then added at a rate of 8 g / min to precipitate fine particles of amorphous resin 6. Then, an aqueous dispersion (amorphous resin 6 fine particle dispersion) containing fine particles of amorphous resin 6 at a concentration of 20% by mass was obtained by removing tetrahydrofuran using an evaporator and adjusting the concentration with the aid of ion exchange water. The 50% particle size (D50) of the fine particles of amorphous resin 6 by volume was 0.14 μm.
[0585] Production Example of Wax Fine Particle Dispersion
[0586] ·100 parts of hydrocarbon wax
[0587] (Fischer-Tropsch wax; peak temperature of maximum endothermic peak in DSC: 90°C)
[0588] Anionic surfactant (Neogen RK manufactured by DKS Co., Ltd.) 5 parts
[0589] ·395 parts of ion exchange water
[0590] The materials listed above were weighed and put into a mixing container equipped with a stirring device, heated to 90° C. and subjected to dispersion treatment for 60 minutes by circulating in Clearmix W-Motion (produced by M Technique Co., Ltd.) The dispersion treatment conditions were as follows.
[0591]
[0592] After the dispersion treatment, an aqueous dispersion (wax fine particle dispersion) in which the concentration of wax (hydrocarbon compound) fine particles is 20 mass % is obtained by cooling to 40°C at a rotor speed of 1000 rpm, a screen speed of 0 rpm and a cooling rate of 10°C / min.
[0593] The 50% particle diameter (D50) by volume of the wax (hydrocarbon compound) fine particles was measured using a dynamic light scattering particle size distribution analyzer (Nanotrac UPA-EX150 manufactured by Nikkiso Co., Ltd.) and found to be 0.15 μm.
[0594] Production Example of Colorant Fine Particle Dispersion Liquid
[0595] ·Colorant 50.0 parts
[0596] (Cyan pigment produced by Dainichiseika Color and Chemicals Mfg. Co., Ltd., Pigment Blue 15:3)
[0597] Anionic surfactant (Neogen RK manufactured by DKS Co., Ltd.) 7.5 parts
[0598] ·442.5 parts of ion exchange water
[0599] An aqueous dispersion liquid (colorant fine particle dispersion liquid) containing colorant fine particles at a concentration of 10 mass % is obtained by weighing out, mixing and dissolving the materials listed above, and dispersing using a Nanomizer high pressure impact disperser (manufactured by Yoshida Kikai Co., Ltd.) for about one hour to disperse the colorant.
[0600] The 50% particle diameter (D50) by volume of the colorant fine particles 1 was measured using a dynamic light scattering particle size distribution analyzer (Nanotrac UPA-EX150 manufactured by Nikkiso Co., Ltd.) and found to be 0.20 μm.
[0601] Production Example of Toner Particles 42
[0602]
[0603] The materials listed above were put into a round stainless steel flask and mixed. Next, a homogenizer (Ultratarax T50 produced by IKA) was used to disperse the obtained mixed solution at 5000r / min for 10 minutes. A 1.0% nitric acid aqueous solution was added to adjust the pH to 3.0, and then the mixed solution was heated to 58°C in a hot water bath while the rotation speed of the stirring blade was appropriately adjusted to stir the mixed solution. The formed aggregated particles were appropriately confirmed using Coulter Multisizer III, and when aggregated particles with a weight-average particle size (D4) of approximately 6.00 μm were formed, the pH was adjusted to 9.0 using a 5% sodium hydroxide aqueous solution.
[0604] The solution was then heated to 75° C. while continuing to stir. The aggregated particles were fused together by maintaining the temperature at 75° C. for one hour.
[0605] Crystallization of the resin was then promoted by cooling to 50°C and maintaining this temperature for three hours.
[0606] The mixture was then cooled to 25° C., filtered, solid-liquid separated, and then washed with ion-exchanged water. After washing, the toner particles 42 having a weight average particle size (D4) of about 6.0 μm were obtained by drying with a vacuum dryer.
[0607] Production Example of Toner 1
[0608] ·Toner particles 1 100 parts
[0609] ·Silica fine particles 1 0.5 parts
[0610] (Silica fine particles treated with hydrophobization having a number average primary particle size of 15 nm)
[0611] ·Silica fine particles 2 1.0 part
[0612] (Silica fine particles treated with hydrophobization having a number average primary particle size of 80 nm)
[0613] The mixture was mixed in an FM-10C Henschel mixer (manufactured by Mitsui Miike Kakoki Corporation) for 30 s. -1 The materials listed above were mixed at a rotation speed of 0.000 and a rotation time of 10 minutes to obtain Toner 1. The physical properties are shown in Table 7-1.
[0614] Production Examples of Toners 2 to 60
[0615] Toners 2 to 60 were obtained by production in the same manner as in the production example of Toner 1, except that the toner particles were changed to those shown in Table 7. The physical properties of the obtained Toners 2 to 60 are shown in Table 7-2 and Table 7-3.
[0616] In addition, in Table 7-1 to Table 7-3, "A" represents the peak temperature (unit: ° C.) of the endothermic peak of tetrahydrofuran-insoluble matter in the toner resin component measured using a differential scanning calorimeter, and "B" represents the endothermic amount ΔHt (unit: J / g) of the endothermic peak.
[0617] [Table 7-1]
[0618]
[0619] [Table 7-2]
[0620]
[0621] [Table 7-3]
[0622]
[0623] Production Example of Magnetic Carrier 1
[0624] Magnetite 1; average particle size: 0.30 μm (magnetization intensity in 1000 / 4π (kA / m) magnetic field: 65 Am 2 / kg)
[0625] Magnetite 2; average particle size: 0.50 μm (magnetization intensity in 1000 / 4π (kA / m) magnetic field: 65 Am 2 / kg)
[0626] 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) is added to 100 parts of each of the materials listed above, and mixed and stirred at a high speed in a container at a temperature of at least 100° C. to process fine particles.
[0627] Phenol: 10% by mass
[0628] Formaldehyde solution: 6 mass% (40 mass% formaldehyde, 10 mass% methanol and 50 mass% water)
[0629] · Magnetite treated with the above-mentioned silane compound 1: 58 mass%
[0630] · Magnetite 2 treated with the above-mentioned silane compound: 26 mass%
[0631] 100 parts of the materials listed above, 5 parts of 28 mass % ammonia aqueous solution and 20 parts of water were put into a flask, heated to 85° C. and maintained at that temperature for 30 minutes while stirring and mixing, polymerization reaction was performed for three hours, and the obtained phenolic resin was cured.
[0632] The cured phenolic resin was then cooled to 30° C., water was added, the supernatant was removed, and the precipitate was washed with water and air-dried.
[0633] Next, a magnetic material dispersed type spherical magnetic carrier 1 was obtained by drying the precipitate under reduced pressure (not more than 5 mmHg) at a temperature of 60° C. The 50% particle diameter (D50) by volume of the magnetic carrier 1 was 34.2 μm.
[0634] Production Example of Two-Component Developer 1
[0635] Two-component developer 1 is obtained by adding 8.0 parts of toner 1 to 92.0 parts of magnetic carrier 1 and mixing using a V-type mixer (V-20 manufactured by Seishin Enterprise Co., Ltd.).
[0636] Production Examples of Two-Component Developers 2 to 66
[0637] Two-component developers 2 to 66 were obtained by production in the same manner as in the production example of the two-component developer 1, except that the toners were changed in the manner shown in Table 8.
[0638] [Table 8]
[0639]
[0640] Example 1
[0641] Two-component developer 1 was used for evaluation.
[0642] A modified printer obtained by modifying an imageRUNNER ADVANCE C5560 commercial digital printer manufactured by Canon Inc. was used as an image forming apparatus, and a two-component developer 1 was introduced into the cyan developing device of the apparatus. The modified apparatus allowed the fixing temperature, process speed, direct current voltage VDC of the developer bearing member, charging voltage VD of the electrostatic latent image bearing member, and laser power to be freely set. Image output evaluation was performed by outputting an FFh image (solid image) having a predetermined image ratio, adjusting VDC, VD, and laser power so that the toner bearing amount of the FFh image on paper was a predetermined value, and performing the following evaluation.
[0643] FFh is a value expressing 256 colors as 16 binary numbers, where 00h represents the 1st grayscale (white background portion) of the 256 colors, and FFh represents the 256th grayscale (solid portion) of the 256 colors.
[0644] Evaluation was performed based on the following evaluation method, and the results are shown in Table 9-1.
[0645] Low temperature fixability
[0646] Paper: GFC-081(81.0g / m 2 )
[0647] (Sold by Canon Marketing Japan KK)
[0648] Toner loading on paper: 0.70 mg / cm 2
[0649] (Adjusted by changing the DC voltage VDC of the developer bearing member, the charging voltage VD of the electrostatic latent image bearing member, and the laser power)
[0650] Evaluation image: Place an image of 2 cm x 5 cm in the center of the A4 paper.
[0651] Test environment: Low temperature and low humidity environment (temperature: 15°C, humidity: 10% RH) (hereinafter referred to as "L / L")
[0652] Fixing temperature: 140℃
[0653] Processing speed: 400mm / sec
[0654] The above evaluation image was output and the low temperature fixability was evaluated. The image density reduction rate was used as an index for evaluating the low temperature fixability.
[0655] The image density reduction rate was determined by first measuring the image density of the central portion of the image using an X-Rite color reflection densitometer (500 series manufactured by X-Rite). Next, a 4.9 kPa (50 g / cm 2 ) load, the fixed image on the portion where the image density had been measured was rubbed with lens cleaning paper (reciprocating five times), and thereafter the image density was measured again.
[0656] Next, the reduction rate of the image density before and after rubbing was calculated using the following formula: The obtained image density reduction rate was evaluated according to the evaluation criteria shown below.
[0657] Image density reduction rate = (image density before rubbing - image density after rubbing) / (image density before rubbing) × 100
[0658] Evaluation Criteria
[0659] AA: Image density reduction rate is less than 1.0%
[0660] A: Image density reduction rate is less than 3.0%
[0661] B: The image density reduction rate is at least 3.0% but less than 5.0%
[0662] C: Image density reduction rate is at least 5.0% but less than 8.0%
[0663] D: Image density reduction rate is at least 8.0%
[0664] Heat stain resistance
[0665] Paper: CS-064 (64.0g / m 2 )
[0666] (Sold by Canon Marketing Japan KK)
[0667] Toner loading on paper: 0.08mg / cm 2
[0668] (Adjusted by changing the DC voltage VDC of the developer bearing member, the charging voltage VD of the electrostatic latent image bearing member, and the laser power)
[0669] Evaluation image: An image of 2 cm × 20 cm in size was placed on the long edge of the A4 paper in the paper passing direction, leaving a 2 mm margin from the edge of the paper.
[0670] Test environment: Normal temperature and low humidity environment (temperature: 23°C, humidity: 5% RH) (hereinafter referred to as "N / L")
[0671] Fixing temperature: from 140℃ in 5℃ increments
[0672] Processing speed: 400mm / sec
[0673] The above-mentioned evaluation image was output, and the hot offset resistance was evaluated based on the following criteria with respect to the maximum fixing temperature at which hot offset did not occur.
[0674] Evaluation Criteria
[0675] AA: at least 175℃
[0676] A: At least 165℃ but less than 175℃
[0677] B: At least 155℃ but less than 165℃
[0678] C: At least 145℃ but less than 155℃
[0679] D: below 145℃
[0680] Winding resistance
[0681] Paper: CS-064 (64.0g / m 2 )
[0682] (Sold by Canon Marketing Japan KK)
[0683] Toner loading on paper: 0.55 mg / cm 2
[0684] (Adjusted by changing the DC voltage VDC of the developer bearing member, the charging voltage VD of the electrostatic latent image bearing member, and the laser power)
[0685] Evaluation image: An image of 2 cm × 20 cm in size was placed on the long edge of the A4 paper in the paper passing direction so as to leave a 2 mm margin from the edge of the paper.
[0686] Test environment: High temperature and high humidity environment (temperature: 30°C, humidity: 80% RH) (hereinafter referred to as "H / H")
[0687] Fixing temperature: from 140℃ in 5℃ increments
[0688] Processing speed: 400mm / sec
[0689] The above-mentioned evaluation image was output, and the wrapping resistance was evaluated based on the following criteria with respect to the maximum fixing temperature at which wrapping did not occur.
[0690] Evaluation Criteria
[0691] AA: at least 175℃
[0692] A: At least 165℃ but less than 175℃
[0693] B: At least 155℃ but less than 165℃
[0694] C: At least 145℃ but less than 155℃
[0695] D: below 145℃
[0696] Scratch resistance
[0697] Paper: Océ Top Coated Pro Silk 270 (270.0 g / m 2 ) (Sold by Océ)
[0698] Evaluation image: Place an image of 2 cm x 15 cm in the center of the A4 paper.
[0699] Toner loading on paper: 0.70 mg / cm 2
[0700] (Adjusted by changing the DC voltage VDC of the developer bearing member, the charging voltage VD of the electrostatic latent image bearing member, and the laser power)
[0701] Test environment: Normal temperature and humidity environment (temperature: 23°C, humidity: 50% RH) (hereinafter referred to as "N / N")
[0702] Fixing temperature: 160℃
[0703] Processing speed: 400mm / s
[0704] Using a HEIDON TYPE 14FW surface property tester produced by Shinto Scientific Co., Ltd., a load of 200 g was applied to the recording paper on which the above evaluation image was output, and then a needle with a diameter of 0.75 mm was used to scratch the image with a length of 30 mm at a speed of 60 mm / min, and then the scratches generated on the image were evaluated.
[0705] In addition, the area ratio of the peeled toner is determined by performing image processing by binarizing the area where the toner is peeled off with respect to the scraped area.
[0706] Evaluation Criteria
[0707] A: No image scratches
[0708] B: The image scraped area ratio of the peeled toner is less than 4.0%
[0709] C: The image scraped area ratio of the peeled toner is at least 4.0% but less than 7.0%
[0710] D: The image scraped area ratio of the peeled toner is at least 7.0%
[0711] Charge Rise Performance
[0712] The evaluation of the charge rise performance is performed by measuring the density change when the output image prints images with different coverage ratios. An image with a low image ratio is output, the charge on the toner in the developer is saturated, and then an image with a high image ratio is output. Therefore, the density change occurs due to the charge difference between the charge saturated toner in the developer and the toner newly supplied to the developer.
[0713] A toner with a fast charge rise property becomes charge saturated immediately after being supplied to a developer, and thus undergoes a small concentration change. However, a toner with a slow charge rise property takes time to become charge saturated after being supplied to a developer, meaning that the charge amount of the entire toner decreases and a concentration change occurs.
[0714] An imagePress C800 full-color copier manufactured by Canon was used as an image forming apparatus, the two-component developer 1 was put into a cyan developing device of the image forming apparatus, and then the following evaluation was performed.
[0715] The modification was carried out so that the mechanism for discharging the excess magnetic carrier in the developing device was removed from the developing device. GF-C081 plain paper (A4, basis weight 81.4 g / m 2 , sold by Canon Marketing Japan) was used as evaluation paper.
[0716] Adjustment was made so that the toner loading amount on paper for FFh images (solid images) was 0.45 mg / cm 2 .
[0717] First, an image output test was conducted by printing 1,000 images at an image ratio of 1%. While continuously feeding 1,000 sheets of paper, the paper was fed under the same conditions as the development conditions and transfer conditions (not calibrated) used when printing the first sheet. The purpose of configuring in this way is to saturate the charge on the toner in the developer.
[0718] Next, an image output test was conducted by printing 1000 sheets of images at an image wall ratio of 80%. While continuously feeding 1000 sheets of paper, the paper was fed under the same development conditions and transfer conditions (not calibrated) as those used when printing the first sheet.
[0719] The image density of the first image printed at an image ratio of 80% was taken as an initial density, and the image density of the 1000th image printed at an image ratio of 80% was measured and evaluated according to the criteria shown below.
[0720] (1) Measurement of image density changes
[0721] Using an X-Rite color reflection densitometer (500 series manufactured by X-Rite), the image density of the first image printed at an image ratio of 80% and the image density of the 1000th image printed at an image ratio of 80% were measured, and the density difference Δ was evaluated according to the following criteria.
[0722] Evaluation criteria: concentration difference Δ
[0723] A: less than 0.03
[0724] B: At least 0.03 but less than 0.06
[0725] C: At least 0.06 but less than 0.10
[0726] D: at least 0.10
[0727] Charging performance (charge retention) in high temperature and high humidity environment -1
[0728] The toner on the electrostatic latent image bearing member was collected by suction using a metal cylindrical pipe and a cylindrical filter, and the triboelectric charge amount of the toner was calculated.
[0729] Specifically, the triboelectric charge amount of the toner on the electrostatic latent image bearing member is measured using a Faraday Cage. The Faraday Cage is a coaxial double cylinder in which the inner cylinder is insulated from the outer cylinder. When a charged body having a charge amount Q is placed in the inner cylinder, it is as if a metal cylinder having a charge amount Q exists due to electrostatic induction. The induced charge amount is measured using an electrometer (Keithley 6517A manufactured by Keithley), and the triboelectric charge amount of the toner is determined by dividing the charge amount Q (mC) by the mass M (kg) of the toner in the inner cylinder, that is, (Q / M).
[0730] Triboelectric charge of toner (mC / kg) = Q / M
[0731] First, an evaluation image for winding resistance is formed on an electrostatic latent image bearing member, and before transferring the image to an intermediate transfer member, the rotation of the electrostatic latent image bearing member is stopped, the toner on the electrostatic latent image bearing member is collected by suction using a metal cylindrical tube and a cylindrical filter, and the "initial Q / M" is measured.
[0732] Next, the developing device was left in the evaluation apparatus in a high temperature and high humidity (H / H) environment (30° C., 80% RH) for 2 weeks, and thereafter the same steps as before the leaving were performed, and the amount of charge per unit mass (Q / M (mC / kg)) on the electrostatic latent image bearing member after the leaving was measured. The value of Q / M per unit mass on the electrostatic latent image bearing member before leaving was represented by “initial Q / M”, and the value of Q / M per unit mass on the electrostatic latent image bearing member after leaving was represented by “Q / M after leaving”, and the value of (“Q / M after leaving” / “initial Q / M”×100) was calculated as the maintenance rate, and judged according to the criteria shown below.
[0733] Evaluation Criteria
[0734] A: The maintenance rate is at least 90%
[0735] B: The maintenance rate is at least 85% but less than 90%
[0736] C: The maintenance rate is at least 80% but less than 85%
[0737] D: The maintenance rate is less than 80%
[0738] Charging performance (charge retention) in high temperature and high humidity environment -2
[0739] The charge retention property was evaluated under a high temperature and high humidity environment more severe than the above-mentioned high temperature and high humidity environment.
[0740] Using a method similar to that used for charge retention in the above-mentioned high temperature and high humidity environment, the "initial Q / M" is measured, and then the developing device is placed in an evaluation device under a higher temperature and higher humidity (SH / SH) environment (40°C, 95% RH) and left for five days. The "Q / M after placement" is measured, and then the value of ("Q / M after placement" / "initial Q / M" × 100) is calculated as the maintenance rate and judged according to the standards shown below.
[0741] Evaluation Criteria
[0742] A: The maintenance rate is at least 90%
[0743] B: The maintenance rate is at least 85% but less than 90%
[0744] C: The maintenance rate is at least 80% but less than 85%
[0745] D: The maintenance rate is less than 80%
[0746] Wipe resistance
[0747] Paper: Image Coat Gloss 158 (158.0 g / m 2 )
[0748] (Sold by Canon Marketing Japan KK)
[0749] Toner loading on paper: 0.05mg / cm 2 (2Fh image)
[0750] (Adjusted by changing the DC voltage VDC of the developer bearing member, the charging voltage VD of the electrostatic latent image bearing member, and the laser power)
[0751] Evaluation image: Place an image of 3 cm x 15 cm in the center of the A4 paper.
[0752] Fixing test environment: Normal temperature and humidity environment (temperature: 23°C, humidity: 50% RH) (hereinafter referred to as "N / N")
[0753] Fixing temperature: 180℃
[0754] Processing speed: 377mm / sec
[0755] The above evaluation image was output and the scratch resistance was evaluated. The difference in reflectivity was used as an index for evaluating the scratch resistance.
[0756] First, a load of 0.5 kgf was applied to the image portion of the evaluation image using a JSPS (Japan Society for the Promotion of Science) type friction fastness tester (AB-301 produced by Tester Sangyo Co., Ltd.), and new evaluation paper was rubbed (reciprocated 10 times). Next, using a reflectometer (REFLECTOMETER MODEL TC-6DS produced by Tokyo Denshoku Co., Ltd.), the reflectivity of the rubbed portion and the reflectivity of the unrubbed portion were measured using the paper on which the evaluation image was rubbed.
[0757] Next, the difference in reflectivity before and after rubbing was calculated using the following formula. The difference in reflectivity obtained was evaluated according to the evaluation criteria shown below. Evaluations of A to C were judged to be good.
[0758] Difference in reflectivity = reflectivity of the unrubbed part - reflectivity of the rubbed part
[0759] Evaluation Criteria
[0760] A: Less than 1.0%
[0761] B: At least 1.0% but less than 2.0%
[0762] C: At least 2.0% but less than 3.0%
[0763] D: At least 3.0%
[0764] Examples 2 to 59 and Comparative Examples 1 to 14
[0765] Evaluation was performed in the same manner as in Example 1, except that two-component developers 2 to 66 were used instead of two-component developer 1. The evaluation results are shown in Table 9-1 and Table 9-2.
[0766] [Table 9-1]
[0767]
[0768] [Table 9-2]
[0769]
[0770] The abbreviations used in Table 9-1 and Table 9-2 are as follows.
[0771] DDR: Concentration reduction rate
[0772] Tem: Temperature
[0773] DDf: concentration difference
[0774] ReR: Maintenance rate
[0775] WBR: White background area ratio
[0776] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. A toner comprising toner particles, wherein the toner particles contain a binder resin comprising a first resin and a second resin, wherein: The first resin is a crystalline resin, The second resin is a non-crystalline resin, The first resin comprises: A first monomer unit represented by the following formula (1); a second monomer unit which is at least one selected from the group consisting of a monomer unit represented by the following formula (3) and a monomer unit represented by the following formula (4); and The third monomer unit represented by the following formula (5), The content ratio of the first monomer unit in the first resin is at least 30.0% by mass. The content ratio of the third monomer unit in the first resin is 20.0 mass % to 50.0 mass %, When the SP value (J / cm 3 ) 0.5 By SP 21 When indicating, SP 21 Satisfies the following formula (2): 21.00≤SP 21 (2) The second resin contains at least one resin selected from the group consisting of a vinyl resin and a hybrid resin in which a vinyl resin and a polyester resin are bonded to each other, An observed cross section of the toner has a domain-matrix structure formed of a matrix including the first resin and a domain including the second resin, The domains have a number average diameter of 0.10 to 2.00 μm, and When SP1(J / cm 3 ) 0.5 is the SP value and SP2 (J / cm 3 ) 0.5 When the SP value of the second resin is 19.0≤SP1, and 0.3≤SP2-SP1≤1.3, In formula (1), R Z1 represents a hydrogen atom or a methyl group, and R represents an alkyl group having 18 to 36 carbon atoms, In formula (3), X represents a single bond or an alkylene group having 1 to 6 carbon atoms, R 1 It means -C≡N; -C(=O)NHR 10 , where R 10 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms; Hydroxyl; -COOR 11 , where R 11 is a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms; -NH-C(=O)-N(R 13 )2, where R 13 The groups are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; -COO(CH2)2NHCOOR 14 , where R 14 is an alkyl group having 1 to 4 carbon atoms; or -COO(CH2)2-NH-C(=O)-N(R 15 )2, where R 15 The groups are each independently a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and R 2 represents a hydrogen atom or a methyl group, In formula (4), R 3 represents an alkyl group having 1 to 4 carbon atoms, and R 4 represents a hydrogen atom or a methyl group, In formula (5), R 5 represents a hydrogen atom or a methyl group, and Ph represents a phenyl group.
2. The toner according to claim 1, wherein in an observed cross section of the toner, A ratio of the area of the domain relative to the area of the cross section of the toner is 15% to 80%.
3. The toner according to claim 1 or 2, wherein when the acid value of the first resin is represented by AVa and the acid value of the second resin is represented by AVi, The values of Ava and AVi satisfy the following equations (6) and (7): 0.5mgKOH / g≤AVa≤30.0mgKOH / g (6) 0.5mgKOH / g≤AVi≤30.0mgKOH / g (7).
4. The toner according to claim 1 or 2, wherein when the acid value of the first resin is represented by AVa and the acid value of the second resin is represented by AVi, the values of Ava and AVi satisfy the formula (8): 0mgKOH / g≤|AVa-AVi|≤20.0mgKOH / g (8).
5. The toner according to claim 1 or 2, wherein when the hydroxyl value of the first resin is represented by OHVa and the hydroxyl value of the second resin is represented by OHVi, the values of OHVa and OHVi satisfy the following formulas (9) and (10): 0.5mgKOH / g≤OHVa≤30.0mgKOH / g (9) 0.5mgKOH / g≤OHVi≤30.0mgKOH / g (10).
6. The toner according to claim 1 or 2, wherein when the hydroxyl value of the first resin is represented by OHVa and the hydroxyl value of the second resin is represented by OHVi, the values of OHVa and OHVi satisfy the following formula (11): 0mgKOH / g≤|OHVa-OHVi|≤20.0mgKOH / g (11). 7 . The toner according to claim 1 , wherein the second resin has a softening point of 120° C. to 160° C.
8. The toner according to claim 1 or 2, wherein The binder resin further contains a third resin, and The third resin includes a resin in which the first resin and the second resin are combined.
9. The toner according to claim 1 or 2, wherein the second resin has a monomer unit represented by the following formula (5): In formula (5), R 5 represents a hydrogen atom or a methyl group, and Ph represents a phenyl group.
10. The toner according to claim 1 or 2, wherein The peak temperature of the endothermic peak of tetrahydrofuran-insoluble matter in the toner other than the inorganic component measured using a differential scanning calorimeter is 55° C. to 80° C., and The endothermic heat amount ΔHt of the endothermic peak is 3 J / g to 30 J / g.
11. The toner according to claim 1 or 2, wherein the vinyl resin is a polymer comprising at least one polymerizable monomer selected from the group consisting of styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-butylstyrene, p-tert-butylstyrene, p-hexylstyrene, p-octylstyrene, p-nonylstyrene, p-decylstyrene, p-laurylstyrene, p-methoxystyrene, p-chlorostyrene, 3,4-dichlorostyrene, m-nitrostyrene, o-nitrostyrene, p-nitrostyrene, acrylic acid, methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, propylene glycol, methoxystyrene, p-chlorostyrene, 3,4-dichlorostyrene, m-nitrostyrene, o-nitrostyrene, p-nitrostyrene, acrylic acid, methyl acrylate, ethyl acrylate, propyl acrylate, n-butyl acrylate, isobutyl acrylate, propylene glycol, n-Octyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, stearyl acrylate, 2-chloroethyl acrylate, phenyl acrylate, methacrylic acid, methyl methacrylate, ethyl methacrylate, propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-octyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, stearyl methacrylate, phenyl methacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, acrylonitrile, methacrylonitrile, acrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 4-(1-hydroxy-1-methylbutyl)styrene and 4-(1-hydroxy-1-methylhexyl)styrene.
12. The toner according to claim 1 or 2, wherein the toner particles contain wax, a first peak and a second peak derived from the wax are present in a temperature difference distribution of an endothermic peak of the toner measured using a differential scanning calorimeter, the peak top temperature of the first peak is at least 70° C., the second peak is adjacent to the first peak, the peak top temperature of the second peak is higher than the peak top temperature of the first peak, and the height of a valley between the first peak and the second peak is greater than 0 W / g.
13. A two-component developer comprising a toner and a magnetic carrier, characterized in that: The toner is the toner according to claim 1 or 2.